Coating composition and coating film
By using aspartate compounds, hydroxyl-containing resin compounds and organic polymer hollow particles in coatings with high solid composition concentration, combined with polyisocyanate composition, the problem of difficult coating viscosity and poor coating film weather resistance is solved, and excellent mattification appearance and low temperature elongation are achieved.
Patent Information
- Application Number
- CN202411480420.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-24
- Filing Date
- 2024-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
Existing coatings contain silica matting agents, which make it difficult to control the viscosity, affecting the coating suitability and appearance of the coating film, especially at low temperatures, the coating film has poor weather resistance.
Aspartate compounds and hydroxyl-containing resin compounds are used as main agents, and organic polymer hollow particles are added thereto as matting agents, and a polyisocyanate composition is combined with a coating composition with a high solid component concentration, controlling viscosity and improving the matting effect and low temperature elongation of the coating film.
It is achieved that the viscosity of the controlled coating is not easily increased at a high solid content concentration of 70% by weight, and the coating film has an excellent mattress appearance and a good elongation at a low temperature of about -20°C.
Smart Images

Figure BDA0005097225020000061 
Figure BDA0005097225020000381 
Figure BDA0005097225020000391
Abstract
Description
Technical Field
[0001] The present invention relates to a coating composition and a coating film. Background Art
[0002] In recent years, in the trend of the times represented by SDGs, companies are also required to carry out activities that are friendly to the global environment, and various initiatives have been promoted in the field of coating materials and paints. For example, one example is the technology that reduces the amount of volatile organic solvents (VOC) discharged during the curing and drying processes of the coating film by increasing the solid content concentration of the coating, thereby reducing the environmental burden. In addition, while reducing the environmental burden, it is also required not to damage the strength and durability of the resulting coating film, thereby improving the strength and durability of the coating film.
[0003] Aspartic acid ester compounds have lower viscosity than when the main agent of the polyurethane coating composition, that is, polyol, is used alone, and the dilution solvent in the polyaspartic acid coating composition can be greatly reduced, thereby enabling a high-solid formulation or a solvent-free formulation to be prepared.
[0004] In addition, since the amino group of the aspartic acid ester compound has a high reactivity with the isocyanate group of either or both of aliphatic and alicyclic polyisocyanates, the polyaspartic acid coating composition has the characteristics of a fast curing speed even at room temperature and excellent mechanical strength compared to the polyurethane coating composition, and its application is expected.
[0005] For example, Patent Document 1 discloses a polyaspartic acid coating composition, which contains an aspartic acid ester compound and a polyisocyanate composition having a predetermined relationship among the contents (mol %) of isocyanurate group, iminooxadiazinedione group, uretdione group, allophanate group and biuret group. In the polyaspartic acid coating composition, the polyisocyanate composition has the following characteristics: curing and drying properties are maintained at a low viscosity suitable for high solid formulation and solvent-free formulation, and the coating film using the polyaspartic acid coating composition is also excellent in chemical resistance, hardness and weather resistance.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2018 / 163953 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, although the polyaspartic acid coating composition disclosed in Patent Document 1 achieves high solids, it does not mention a method for obtaining a matte appearance that enables the composition to be used in the field of outer packaging.
[0011] Generally, silica is used as a matting agent for coatings. For coatings containing silica, the effect of hydrogen bonding between silicas can be weakened by diluting with a solvent (solvent), and its viscosity can be controlled to a range suitable for coating. On the other hand, in high-solid formulations and solvent-free formulation coatings, the content of solvent (solvent) is small, so the content of silica becomes relatively high, and the hydrogen bonding between silicas is strong, resulting in problems such as high viscosity of the coating, inability to obtain coating suitability, and poor appearance of the coating film.
[0012] The suitable range of coating viscosity varies depending on the performance of various coating machines. For coatings containing matting agents such as silica, the suitable viscosity range during coating is preferably 20,000 mPa·s or less from the viewpoint of improving coating suitability and coating film appearance. However, as the content of silica increases, the viscosity tends to increase, making it difficult to control the viscosity. In addition, it is known that coatings containing a large amount of matting agent tend to have poor elongation at low temperatures of about -20°C, which leads to poor weather resistance and other deterioration over time.
[0013] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coating composition having excellent matting effect per unit compounding amount of a matting agent and, in addition, having a high solid content concentration of 70% by weight or more, which is not likely to increase the viscosity. Another object is to provide a coating film having good elongation at a low temperature of about -20°C.
[0014] In addition, the present invention aims to provide a coating base agent which is a coating base agent having a solid content concentration of 70% by weight or more and can provide a coating composition having a suppressed viscosity increase and excellent matte appearance, a coating composition using the same, a coating film, a coating curing agent, and a method for imparting a matte appearance to a cured product of a coating composition.
[0015] Solutions for solving problems
[0016] That is, the present invention includes the following aspects.
[0017] [1] A coating composition comprising a main agent, a matting agent (B), and a polyisocyanate composition (C), wherein the main agent comprises one or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), the matting agent (B) is contained in an amount of 1% by weight or more and 40% by weight or less relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2), and the polyisocyanate composition (C), the coating composition has a solid content concentration of 70% by weight or more, the polyisocyanate composition (C) comprises a polyisocyanate component (C-1), the polyisocyanate component (C-1) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, and a polyester polyol having an average functional group number of 2 or 3 of hydroxyl groups, and the polyisocyanate component (C-1) has a molar ratio of urethane group / allophanate group of 100 / 0 to 75 / 25.
[0018] [2] A coating composition comprising a main agent, a matting agent (B), and a polyisocyanate composition (C), wherein the main agent comprises one or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), the content of the matting agent (B) is 1% by weight or more and 40% by weight or less relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2), and the polyisocyanate composition (C), and the solid content concentration of the coating composition is 70% by weight or less. % by weight or more, the polyisocyanate composition (C) comprises a polyisocyanate component (C-2), the polyisocyanate component (C-2) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a polyester polyol having an average functional group number of hydroxyl groups of 2 or 3, and a polyoxyalkylene polyol having an average functional group number of hydroxyl groups of 2 to 4, and the molar ratio of carbamate group / alophanate group of the polyisocyanate component (C-2) is 100 / 0 to 75 / 25.
[0019] [3] The coating composition according to [1] or [2], wherein the matting agent (B) is at least one selected from the group consisting of inorganic fine particles (B-1), organic polymer fine particles (B-2), organic polymer hollow particles (B-3) and wax particles (B-4).
[0020] [4] A coating composition according to any one of [1] to [3], wherein the polyisocyanate composition (C) further comprises a polyisocyanate component (C-3), wherein the polyisocyanate component (C-3) is obtained from at least one diisocyanate selected from aliphatic diisocyanates and alicyclic diisocyanates and a monohydric alcohol having 1 to 20 carbon atoms, and the molar ratio of the allophanate group to the isocyanurate group (allophonate group / isocyanurate group) of the polyisocyanate component (C-3) is 100 / 0 to 70 / 30.
[0021] [5] The coating composition according to any one of [1], [3] and [4], wherein the molar ratio of the urethane group / allophanate group of the polyisocyanate component (C-1) is 99 / 1 to 90 / 10.
[0022] [6] The coating composition according to any one of [2] to [4], wherein the molar ratio of urethane group / allophanate group in the polyisocyanate component (C-2) is 99 / 1 to 90 / 10.
[0023] [7] A coating film formed by curing the coating composition according to any one of [1] to [6].
[0024] That is, the present invention includes the following aspects.
[0025] [8] A main agent for coating, comprising either or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), and organic polymer hollow particles (B-3), wherein the true specific gravity of the organic polymer hollow particles (B-3) is greater than or equal to 0.01 and less than or equal to 0.30, the average particle size is greater than or equal to 1 μm and less than or equal to 100 μm, and the content thereof is greater than or equal to 10% by weight and less than or equal to 200% by weight relative to the total amount of either or both of the aspartic acid ester compound (A-1) and the hydroxyl-containing resin compound (A-2), and the solid content concentration of the main agent for coating is greater than or equal to 70% by weight.
[0026] [9] A main agent for coating according to [8], wherein the organic polymer hollow particles (B-3) are either or both of hollow particles consisting of an outer shell portion comprising a thermoplastic resin and a hollow portion surrounded by the outer shell portion, and particles whose surfaces are further coated with a thermosetting resin.
[0027]
[10] A coating composition comprising the coating base according to [8] or [9] and a polyisocyanate composition (C1), wherein the coating composition has a solid content concentration of 70% by weight or more.
[0028]
[11] A coating film formed by curing the aqueous coating composition described in
[10] .
[0029]
[12] A coating curing agent comprising a polyisocyanate composition (C1) and organic polymer hollow particles (B-3), wherein the true specific gravity of the organic polymer hollow particles (B-3) is greater than 0.01 and less than 0.30, the average particle size is greater than 1 μm and less than 100 μm, and the content thereof is greater than 10 wt % and less than 200 wt % relative to the total amount of the polyisocyanate composition (C1), and the solid content concentration of the coating curing agent is greater than 70 wt %.
[0030]
[13] A method for imparting a matte appearance to a cured product of a coating composition, comprising adding organic polymer hollow particles (B-3) having a true specific gravity of not less than 0.01 and not more than 0.30 and an average particle size of not less than 1 μm and not more than 100 μm as a matting agent to the coating composition, wherein the coating composition comprises either or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), and a polyisocyanate composition (C1).
[0031] Effects of the Invention
[0032] According to the present invention, a coating composition can be provided which has excellent matting effect per unit compounding amount of a matting agent and which is not likely to increase viscosity even in a coating having a high solid content concentration of 70 wt % or more. In addition, a coating film having good elongation at a low temperature of about -20°C can be provided.
[0033] In addition, according to the present invention, there can be provided a coating base agent which is a coating base agent having a solid content concentration of 70% by weight or more and which can provide a coating composition having a suppressed viscosity increase and having an excellent matte appearance, a coating composition using the same, a coating film, a coating curing agent, and a method for imparting a matte appearance to a cured product of a coating composition. DETAILED DESCRIPTION
[0034] Hereinafter, a mode for implementing the present invention (hereinafter referred to as "this embodiment") will be described in detail. It should be noted that the present invention is not limited to the following this embodiment. The present invention can be implemented by appropriately modifying it within the scope of its gist.
[0035] <Coating composition>
[0036] The present invention is a coating composition, which comprises a main agent, a matting agent (B), and a polyisocyanate composition (C).
[0037] The main agent contains either or both of the aspartic acid ester compound (A-1) and the hydroxyl group-containing resin compound (A-2).
[0038] In one embodiment of the present invention, the polyisocyanate composition (C) contains a polyisocyanate component (C-1), wherein the polyisocyanate component (C-1) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates and a polyester polyol having an average functional group number of 2 or 3 of hydroxyl groups, and the molar ratio of carbamate group / alophanate group of the polyisocyanate component (C-1) is 100 / 0 to 75 / 25.
[0039] In one embodiment of the present invention, the polyisocyanate composition (C) contains a polyisocyanate component (C-2), wherein the polyisocyanate component (C-2) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a polyester polyol having an average functional group number of 2 or 3 for hydroxyl groups, and a polyoxyalkylene polyol having an average functional group number of 2 to 4 for hydroxyl groups, and the molar ratio of urethane group / alophanate group of the polyisocyanate component (C-2) is 100 / 0 to 75 / 25.
[0040] Next, each constituent component contained in the coating composition of the present embodiment will be described in detail below.
[0041] Main Ingredients
[0042] (Aspartic acid ester compound (A-1))
[0043] The aspartic acid ester compound (A-1) used in the present embodiment is an aspartic acid ester compound represented by the following formula (I).
[0044]
[0045] [In formula (I), X is an n-valent organic group obtained by removing the primary amino group of an n-valent polyamine, and R 1 and R 2 is the same or different organic group that is inactive to isocyanate groups under the reaction conditions, and n is an integer greater than 2.
[0046] (X)
[0047] In the general formula (I), X is an n-valent organic group.
[0048] As the n-valent organic group, it can be an aliphatic group or an aromatic group. The aliphatic group can be any of a straight chain, a branched chain or a cyclic group. In addition, n is an integer greater than 2 as described later.
[0049] Examples of the linear or branched aliphatic group include an alkanediyl group (alkylene group), an alkylidene group (alkylidene group), and an alkylidene group (alkylidyne group).
[0050] Examples of the cyclic aliphatic group include a cycloalkylene group and the like.
[0051] Examples of the aromatic group include arylene groups such as phenylene group.
[0052] More specifically, from the viewpoint of the yellowing resistance of the coating composition of the present embodiment, X is preferably a linear, branched or cyclic divalent aliphatic group having a carbon number of 2 or more and 20 or less. Examples of the linear, branched or cyclic divalent aliphatic group having a carbon number of 2 or more and 20 or less include n-butylene, n-pentylene, n-hexylene, 2,2,4-trimethylhexamethylene, 2,4,4-trimethylhexamethylene, 3,3,5-trimethyl-5-methylcyclohexylene, dicyclohexylmethylene, and 3,3'-dimethyldicyclohexylmethylene.
[0053] (R 1 and R 2 )
[0054] In the general formula (I), R 1 and R 2 Each is independently an organic group which is inactive towards isocyanate groups under the reaction conditions.
[0055] It should be noted that, in this specification, “inactive with respect to isocyanate groups under reaction conditions” means that R 1 and R 2 It does not have a Zerewitinoff-active hydrogen-containing group such as a hydroxyl group, an amino group, or a mercapto group (CH acidic compound).
[0056] R 1 and R 2 Each independently is preferably an alkyl group having 1 to 10 carbon atoms, and more preferably a methyl group, an ethyl group, a propyl group or a butyl group.
[0057] R 1 and R 2 Can be the same or different.
[0058] (n)
[0059] In the general formula (I), n is an integer of 2 or more.
[0060] Among them, n is preferably an integer of 2 to 6, more preferably an integer of 2 to 4, further preferably 2 or 3, and particularly preferably 2.
[0061] The aspartic acid ester compound represented by formula (I) can be produced by the method described in International Publication No. 2018 / 163959.
[0062] (Hydroxy-containing resin compound (A-2))
[0063] The hydroxyl-containing resin compound (A-2) used in the present embodiment can include polyester polyols, polyether polyols, acrylic polyols, polyolefin polyols, fluorine polyols, polycarbonate polyols, polyurethane polyols, etc. These hydroxyl-containing resin compounds can include one alone or two or more in combination. Among them, as the hydroxyl-containing resin compound, acrylic polyols or polyester polyols are preferred.
[0064] The main agent contains either or both of the aspartic acid ester compound (A-1) and the hydroxyl-containing resin compound (A-2). In other words, the main agent may contain the aspartic acid ester compound (A-1) alone, the hydroxyl-containing resin compound (A-2) alone, or both the aspartic acid ester compound (A-1) and the hydroxyl-containing resin compound (A-2).
[0065] Matting Agent (B)
[0066] The matting agent (B) used in the present embodiment is preferably at least one selected from the group consisting of inorganic fine particles (B-1), organic polymer fine particles (B-2), organic polymer hollow particles (B-3) and wax particles (B-4).
[0067] The content of the matting agent (B) is 1% by weight or more and 40% by weight or less, more preferably 5% by weight or more and 35% by weight or less, further preferably 10% by weight or more and 30% by weight or less, and particularly preferably 10% by weight or more and 25% by weight or less, relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2) and the polyisocyanate composition (C). By setting the content of the matting agent (B) within the above range, it is possible to achieve both viscosity control of the coating composition and coating film properties. Coating film properties refer to properties that are excellent in matting properties and elongation at low temperatures of about -20°C.
[0068] Inorganic particles (B-1)
[0069] The inorganic particles (B-1) used in this embodiment have an average particle size of 1 μm or more and 20 μm or less. The average particle size is preferably 2 μm or more and 15 μm or less, more preferably 3 μm or more and 10 μm or less. By making the average particle size within the above range, the surface of the coating film presents an appropriate surface roughness by utilizing the inorganic particles that are biased toward the surface of the coating film, thereby obtaining excellent matte properties.
[0070] As inorganic particles (B-1), for example, silica particles, alumina particles, titanium oxide particles, zirconium oxide particles, zircon particles, tin oxide particles, magnesium oxide particles, or mixtures thereof can be cited. Among them, in particular, from the viewpoints of extinction ability, storage stability, etc., the inorganic particles are preferably silica particles. The shape of the aforementioned silica particles is not particularly limited, and spherical, hollow, porous, rod-shaped, plate-shaped, fibrous or irregularly shaped particles can be used.
[0071] Examples of commercially available silica particles include SYLYSIA series ("SYLYSIA350", "SYLYSIA430", "SYLYSIA435", "SYLYSIA436", "SYLYSIA450", etc.), SYLOPHOBIC series ("SYLOPHOBIC100", "SYLOPHOBIC200", "SYLOPHOBIC702", "SYLOPHOBIC4004", etc.), SYLOSPHERE series ("SYLOSPHERE1504", "SYLOSPHERE1510", etc.), SYLOID series ("SYLOID W300", "SYLOID W500", etc.) manufactured by Grace Japan Co., Ltd., and ACEMATT series ("ACEMATT HK460", "ACEMATT HK400", "ACEMATT OK412", "ACEMATT TS10", "ACEMATT 3200", "ACEMATT 3300", "ACEMATT3600", etc.), NIPGEL series ("NIPGEL AZ-200", etc.), NIPSIL series ("NIPSIL E-200A", "NIPSIL SS-50B", "NIPSIL SS-178B", etc.) manufactured by Nippon Silica Industries, Ltd., mizukasil series ("mizukasil P-73", "mizukasil P-526", etc.) manufactured by Mizusawa Chemical Co., Ltd., CARPLEX series ("CARPLEX CS-8", etc.) manufactured by Shionogi Pharmaceutical Co., Ltd., AEROSIL series ("AEROSIL 200", "AEROSIL R805", "AEROSIL R972", etc.) manufactured by Nippon AEROSIL Co., Ltd., and Radiolite series ("Radiolite 100", "Radiolite 200", "Radiolite 500", "Radiolite 500R", "Radiolite 500RS", etc.) manufactured by Showa Chemical Industry Co., Ltd.
[0072] As the above-mentioned inorganic particles (B-1), untreated inorganic particles may be used, or inorganic particles surface-treated with organic compounds or inorganic compounds may be used. Among them, from the viewpoints of alkali resistance, extinction stability, etc., preferably inorganic particles are organically treated, and organically treated silica particles are particularly preferred. As treatment using organic compounds, polyethylene treatment, polyethylene wax treatment, hydrophobic surface treatment, etc. may be cited.
[0073] Organic polymer microparticles (B-2)
[0074] The organic polymer microparticles (B-2) used in this embodiment have an average particle size of 10 μm or more and 100 μm or less. The average particle size of the organic polymer microparticles (B-2) is preferably 10 μm or more and 90 μm or less, more preferably 15 μm or more and 70 μm or less. By making the average particle size within the above range, the surface of the coating film presents an appropriate surface roughness by utilizing the organic polymer microparticles that are predominantly present on the surface of the coating film, thereby obtaining excellent matte properties.
[0075] The organic polymer particles (B-2) include, for example, at least one selected from the group consisting of styrene resin particles, acrylic resin particles, polyurethane resin particles, urea resin particles, polyester resin particles, and vinyl butyral resin particles, preferably at least one selected from the group consisting of acrylic resin particles, polyurethane resin particles, and urea resin particles. By making the organic polymer particles (B-2) include such particles, a coating composition is provided that does not easily increase the viscosity even in a coating with a high solid content concentration of 70% or more and has an excellent matte appearance. In addition, the coating film formed by curing the above-mentioned coating composition has good chemical resistance.
[0076] ··Styrene resin particles or acrylic resin particles
[0077] The aforementioned styrene resin particles or acrylic resin particles include styrene resin or acrylic resin, and the styrene resin or acrylic resin may be a polymer of an ethylenically unsaturated monomer.
[0078] As the aforementioned ethylenically unsaturated monomer, a monomer having two or more ethylenically unsaturated bonds in one molecule can be used. As the aforementioned monomer having two or more ethylenically unsaturated bonds in one molecule, there is no particular limitation, and examples thereof include ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerol di(meth)acrylate. unsaturated monocarboxylic acid esters of polyhydric alcohols such as esters of glycerol di(meth)acrylate, glycerol allyloxy di(meth)acrylate, 1,1,1-trimethylolethane di(meth)acrylate, 1,1,1-trimethylolethane tri(meth)acrylate, 1,1-trimethylolpropane di(meth)acrylate, 1,1,1-trimethylolpropane tri(meth)acrylate; unsaturated alcohol esters of polybasic acids such as triaryl cyanurate, triaryl isocyanurate, triaryl trimellitate, diaryl terephthalate, diaryl phthalate; aromatic monomers substituted with two or more vinyl groups such as divinylbenzene, etc.
[0079] Specific examples of the styrene resin particles or acrylic resin particles are not particularly limited, and examples thereof include epostar MA1002, epostar MA1004, epostar MA1006, and epostar MA1010 (manufactured by Nippon Shokubai Co., Ltd.), TAFTIC FH-S005, TAFTIC FH-S008, TAFTIC FH-S010, TAFTIC FH-S015, TAFTIC FH-S020, TAFTIC AR650SX, TAFTIC AR650S, TAFTIC AR650M, and TAFTIC AR650MX (manufactured by Toyobo Co., Ltd.), Techpolymer MBX-8, Techpolymer MBX-20, and Techpolymer MBX-40 (manufactured by Sekisui Chemicals Co., Ltd.), and Chemisnow MX-80H3wT, MX-150, MX-180TA, MX-300, MX-500, MX-1000, MX-1500H, MX-2000, MX-3000 (manufactured by Soken Chemical Co., Ltd.), epostar MA2003 (manufactured by Nippon Shokubai Co., Ltd.), etc.
[0080] ··Polyurethane resin particles
[0081] The polyurethane resin particles include a urethane resin, which may be a reaction product of a polyol and a polyisocyanate and, if necessary, a chain extender and / or a chain terminator.
[0082] Examples of the polyol include polymer polyols such as polyether polyol, polyester polyol, polycarbonate polyol, and glycerol polycaprolactone triol; and low molecular weight polyols. The number average molecular weight of the polymer polyol may be, for example, 300 to 5,000, or further 500 to 3,000. In addition, the number of hydroxyl groups contained in the polymer polyol may be 2 to 3.
[0083] Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and the like; examples of the polyester polyol include polybutylene adipate, polyhexamethylene adipate, polyneopentyl adipate, and the like; and examples of the polycarbonate polyol include polycaprolactone diol, poly-3-methylvalerolactone diol, polyhexamethylene carbonate, and the like.
[0084] Examples of the low molecular weight polyols include aliphatic polyols such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, butanediol, pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, cyclohexanediol, hexanediol, dicyclohexane dimethanol, hydrogenated bisphenol A, and cyclohexanetriol; aromatic polyols such as bisphenol A, bisphenol F, and bisphenol AD, and ethylene oxide adducts or propylene oxide adducts of the bisphenol compounds; triols such as trimethylolpropane and trimethylolethane; and polyols having a carboxyl group such as dimethylolacetic acid, dimethylolpropionic acid, and dimethylolbutyric acid.
[0085] Examples of the chain extender include the low molecular weight polyols described above; polyamine compounds such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, cyclohexanediamine, isophoronediamine, dicyclohexylmethanediamine, bis(aminomethyl)cyclohexane, hydrazine, toluenediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.
[0086] Examples of the chain terminator include methanol, ethanol, propanol, butanol, ammonia, dibutylamine, and aminosilane.
[0087] Specific examples of polyurethane resin fine particles are not particularly limited, and examples include cross-linked urethane beads such as ART PEARL C-1000 transparent, ART PEARL C-600 transparent, ART PEARL C-400 transparent, ART PEARL C-800, ART PEARL MM-120T, ART PEARL JB-800T, ART PEARL JB-600T, ART PEARL P-800T, and ART PEARL P-400T (manufactured by Negami Industries, Ltd.).
[0088] ··Urea resin granules
[0089] The urea resin granules include urea resin, which may be a reaction product of urea and aldehyde. The urea resin granules may be in a powdery form, or may be produced by pulverizing the urea resin.
[0090] As the aldehyde component, formaldehyde, acetaldehyde, crotonaldehyde, benzaldehyde, etc. can be used. Among them, formaldehyde is suitable because the condensation reaction easily proceeds.
[0091] Specific examples of the urethane resin fine particles are not particularly limited, and examples thereof include Pergopak M3, Pergopak M4, and Pergopak M5 (manufactured by Huber Advanced Materials Co., Ltd.), and SOOFINE JJ POWDER (manufactured by Hangzhou Jingcai Chemical Co., Ltd.).
[0092] ··Polyester resin particles
[0093] The polyester resin particles include polyester resins, and the polyester resins include reaction products of polyols and polycarboxylic acids. The polyols include compounds exemplified as the low molecular weight polyols. The polycarboxylic acids include succinic acid (anhydride), phthalic acid (anhydride), isophthalic acid, terephthalic acid, adipic acid, sebacic acid, hexahydrophthalic acid (anhydride), trimellitic acid (anhydride), pyromellitic acid (anhydride), etc. The acid value of the polyester resin particles may be 100 mgKOH / g or less.
[0094] ··Polyvinyl butyral resin particles
[0095] The vinyl butyral resin particles include polyvinyl butyral resin, and the polyvinyl butyral resin may be a reaction product of polyvinyl alcohol and butyraldehyde. The reaction of polyvinyl alcohol and butyraldehyde may be carried out under acidic conditions.
[0096] (Organic polymer hollow particles (B-3))
[0097] The true specific gravity of the organic polymer hollow particles (B-3) used in this embodiment is 0.01 or more and 0.30 or less. The true specific gravity is preferably 0.05 or more and 0.30 or less, and more preferably 0.10 or more and 0.25 or less. By making the true specific gravity within the above range, the organic polymer hollow particles are more heavily present on the surface of the coating film during the coating film formation process. Thus, a coating film having a more excellent matting property than the case of using a conventional matting agent can be obtained.
[0098] The above-mentioned organic polymer hollow particles (B-3) have an average particle size of 1 μm or more and 100 μm or less. The average particle size is preferably 5 μm or more and 90 μm or less, more preferably 10 μm or more and 70 μm or less. When the average particle size is within the above range, the surface of the coating film presents an appropriate surface roughness by utilizing the organic polymer hollow particles that are predominantly present on the surface of the coating film, thereby obtaining excellent matte properties.
[0099] The organic polymer hollow particles (B-3) preferably include particles composed of an outer shell portion composed of a thermoplastic resin (b-1) and a hollow portion surrounded by the outer shell portion, or particles whose surfaces are further covered with a thermosetting resin (b-2).
[0100] The thermoplastic resin (b-1) is not particularly limited, but is preferably a polymer containing a monomer component as a monomer having one polymerizable carbon-carbon double bond and optionally containing a polymerizable component as a crosslinking agent as a monomer having at least two polymerizable carbon-carbon double bonds. Examples of the monomer components contained in the polymerizable component include nitrile monomers such as acrylonitrile, methacrylonitrile, fumaronitrile, and maleonitrile; halogenated vinyl monomers such as vinyl chloride; halogenated vinylidene monomers such as vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl butyrate; unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, crotonic acid, and cinnamic acid; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, fumaric acid, citraconic acid, and chloromaleic acid; anhydrides of unsaturated dicarboxylic acids; unsaturated dicarboxylic acid monoesters such as monomethyl maleate, monoethyl maleate, monobutyl maleate, monomethyl fumarate, monoethyl fumarate, monomethyl itaconate, monoethyl itaconate, and monobutyl itaconate; and carboxyl group-containing monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (Meth)acrylate monomers such as stearyl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate; (meth)acrylamide monomers such as acrylamide, substituted acrylamide, methacrylamide, substituted methacrylamide; maleimide monomers such as N-phenylmaleimide and N-cyclohexylmaleimide; styrene monomers such as styrene and α-methylstyrene; ethylenically unsaturated monoolefin monomers such as ethylene, propylene, and isobutylene; vinyl ether monomers such as vinyl methyl ether, vinyl ethyl ether, and vinyl butyl ether; vinyl ketone monomers such as vinyl methyl ketone; N-vinyl carbazole, N-vinyl pyrrolidone, and other N-vinyl naphthalene monomers such as 1-vinylnaphthalene and 2-vinylnaphthalene; itaconic acid diesters such as dimethyl itaconate and dibutyl itaconate, etc. Some or all of the carboxyl groups of the carboxyl group-containing monomers may be neutralized during or after polymerization. These monomer components may be used alone or in combination of two or more.
[0101] The thermosetting resin (b-2) is not particularly limited, and is preferably, for example, one or more selected from the group consisting of melamine formaldehyde resins, phenol formaldehyde resins, urea formaldehyde resins, and epoxy resins.
[0102] The organic polymer hollow particles (B-3) may be composite hollow particles having inorganic fine powder attached to the surface.
[0103] The hollow part has a void space. The void space may contain a substance such as a gas. The gas is not particularly limited, and inorganic gases such as nitrogen, oxygen, and air, and organic gases such as hydrocarbons may be cited.
[0104] The organic polymer hollow particles (B-3) are not particularly limited, and examples thereof include trade names such as "Matsumoto Microsphere F-30E", "Matsumoto Microsphere F-50E", "Matsumoto Microsphere F-65E", "Matsumoto Microsphere FN-80SDE", "Matsumoto Microsphere F-65DE", "Matsumoto Microsphere F-80DE", "Matsumoto Microsphere F-78DE", "Matsumoto Microsphere MFL-81GTA", "Matsumoto Microsphere MFL-81CGA", "Matsumoto Microsphere MFL-HD30CA", "Matsumoto Microsphere MFL-60CA", "Matsumoto Microsphere MFL-UPR60", "Matsumoto Microsphere MFL-100MCA", and "Matsumoto Microsphere MFL-110CAL" manufactured by Matsumoto Oil & Pharmaceutical Co., Ltd.
[0105] (Wax particles)
[0106] The wax particles (B-4) used in this embodiment have an average particle size of 10 μm or more and 100 μm or less. The average particle size is preferably 10 μm or more and 90 μm or less, and more preferably 15 μm or more and 70 μm or less. By making the average particle size within the above range, the surface of the coating film presents an appropriate surface roughness by utilizing the wax particles that are predominantly present on the surface of the coating film, thereby obtaining excellent matte properties.
[0107] Examples of the polyolefin wax include polyethylene wax, modified polyethylene wax, amide-modified polyethylene wax, PTFE-modified polyethylene wax, polypropylene wax, and modified polypropylene wax.
[0108] Specific examples of the wax particles (B-4) include, but are not particularly limited to, CERAFLOUR913, CERAFLOUR914, CERAFLOUR915, CERAFLOUR916, CERAFLOUR917, CERAFLOUR925, CERAFLOUR927, CERAFLOUR929, CERAFLOUR950, CERAFLOUR970, CERAFLOUR981R, CERAFLOUR988, CERAFLOUR991, CERAFLOUR994, CERAFLOUR996R, CERAFLOUR997R, CERAFLOUR998R, CERAFLOUR1000, and MP GOKYO FOOD & CHEMICAL Co., Ltd.; Viscol330-P, Viscol440-P, Viscol550-P, Viscol660-P, SANWAX161-P, SANWAX131-P, SANWAX151-P, SANWAX171-P; S-379H, S-379N8, S-394MG, S-394N1, S-394N5, S-395N2, S-395N5, S-395SP5, S-363, etc. manufactured by Shamrock Technologies.
[0109] 《Polyisocyanate composition (C)》
[0110] The polyisocyanate composition (C) used in the present embodiment contains a polyisocyanate component (C-1) or (C-2) described later.
[0111] 《Polyisocyanate component (C-1)》
[0112] The polyisocyanate component (C-1) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates and a polyester polyol having an average hydroxyl functional group number of 2 or 3, and the molar ratio of urethane group / allophanate group is 100 / 0 to 75 / 25.
[0113] 《Polyisocyanate component (C-2)》
[0114] The polyisocyanate component (C-2) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a polyester polyol having an average functional group number of 2 or 3 for hydroxyl groups, and a polyoxyalkylene polyol having an average functional group number of 2 to 4 for hydroxyl groups, and the molar ratio of carbamate group / alophanate group is 100 / 0 to 75 / 25.
[0115] The aliphatic diisocyanate is not limited to the following substances, and examples thereof include 1,4-diisocyanatobutane, 1,5-diisocyanatopentane (hereinafter sometimes referred to as "PDI"), ethyl (2,6-diisocyanato)hexanoate, 1,6-diisocyanatohexane (hereinafter sometimes referred to as "HDI"), 1,9-diisocyanatononane, 1,12-diisocyanatododecane, 2,2,4- or 2,4,4-trimethyl-1,6-diisocyanatohexane, etc. These aliphatic diisocyanates may be used alone or in combination of two or more.
[0116] The alicyclic diisocyanate is not limited to the following, and examples thereof include 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (hereinafter sometimes referred to as "hydrogenated XDI"), 1,3- or 1,4-diisocyanatocyclohexane, 3,5,5-trimethyl-1-isocyanato-3-(isocyanatomethyl)cyclohexane (hereinafter sometimes referred to as "IPDI"), 4-4'-diisocyanato-dicyclohexylmethane (hereinafter sometimes referred to as "hydrogenated MDI"), 2,5- or 2,6-diisocyanatomethylnorbornane, etc. These alicyclic diisocyanates may be used alone or in combination of two or more.
[0117] These aliphatic diisocyanates and alicyclic diisocyanates may be used alone or in combination of two or more.
[0118] Among them, as the diisocyanate, PDI, HDI, IPDI, hydrogenated XDI, or hydrogenated MDI is preferred, PDI, HDI, or IPDI is more preferred, and HDI is further preferred.
[0119] In the production of the polyisocyanate, in addition to the above-mentioned diisocyanate, an isocyanate monomer as shown below may be further used.
[0120] (1) Aromatic diisocyanates such as diphenylmethane-4,4'-diisocyanate (MDI), 1,5-naphthalene diisocyanate, toluene diisocyanate (TDI), xylylene diisocyanate (XDI), and m-tetramethylxylylene diisocyanate (TMXDI).
[0121] (2) Triisocyanates such as 4-isocyanatomethyl-1,8-octamethylene diisocyanate (hereinafter sometimes referred to as “NTI”), 1,3,6-hexamethylene triisocyanate (hereinafter sometimes referred to as “HTI”), bis(2-isocyanatoethyl) 2-isocyanatoglutarate (hereinafter sometimes referred to as “GTI”), and lysine triisocyanate (hereinafter sometimes referred to as “LTI”).
[0122] (Polyester polyol)
[0123] The polyester polyol is a divalent and / or trivalent polyol containing a repeating unit represented by -O(CH2)5CO-, and can be derived from a divalent and / or trivalent alcohol and ε-caprolactone, etc. In addition, there is no particular limitation, and for example, a divalent and / or trivalent alcohol can be used as an initiator to obtain the polyester polyol by ring-opening polymerization of ε-caprolactone, etc. in the presence of a catalyst.
[0124] In addition, polyester polyols having an average number of functional groups of 2 and / or 3 can be obtained by condensing a single dibasic acid or a mixture of two or more dibasic acids with a single polyol or a mixture of two or more polyols using a divalent and / or trivalent alcohol as an initiator.
[0125] Examples of the dibasic acid include succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, 1,4-cyclohexanedicarboxylic acid, succinic anhydride, maleic acid, phthalic acid, glutaric acid, suberic acid, azelaic acid, succinic acid, sebacic acid, itaconic acid, itaconic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, tetrahydrophthalic acid, and tetrahydrophthalic anhydride.
[0126] Examples of the polyol include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, trimethylpentanediol, cyclohexanediol, 2-ethyl-1,3-hexanediol, trimethylolpropane, glycerol, pentaerythritol, 2-hydroxymethylpropanediol, epoxidized trimethylolpropane, 1,3-propanediol, pentane-1,5-diol, heptane-1,7-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol, dodecanedioic acid, and the like. 1,12-diol, cyclohexane-1,4-dimethanol, 4,4'-(1-methylethylidene)bicyclohexanol, 1,1,1-trimethylolethane, hexane-1,2,6-triol, dipropylene glycol, propane-1,2-diol, butane-1,3-diol, hexane-1,2-diol, 2-methylpentane-2,4-diol, 3-methylpentane-1,5-diol, octane-1,2-diol, 2-butyl-2-ethylpropane-1,3-diol, decane-1,2-diol, etc.
[0127] The polyester polyol having an average functional group number of 2 and / or 3 is preferably a polycaprolactone polyol having an average functional group number of 2 and / or 3, a polyester polyol which is a condensate of a dibasic acid having an average functional group number of 2 and / or 3 and a polyol, or a mixture thereof.
[0128] When the polyisocyanate composition using a polyester polyol having an average functional group number of 2 and / or 3 is used as a curing agent and an aspartic acid ester compound is used as a main agent, the compatibility of the main agent and the curing agent becomes high. Therefore, the polyisocyanate composition of the present embodiment can be suitably used as a curing agent for a polyaspartic acid coating composition having an aspartic acid ester compound as a main agent.
[0129] When a polyester polyol having an average number of functional groups of 2 and / or 3 is used, high flexibility can be exerted by three-dimensional crosslinking including physical crosslinking, and a coating film having high elongation can be produced.
[0130] The number average molecular weight of the polyester polyol having an average number of functional groups of 2 and / or 3 is preferably 250 or more and 4000 or less. The number average molecular weight is more preferably 250 or more and 1500 or less, further preferably 250 or more and 1000 or less, and particularly preferably 300 or more and 800 or less. When the number average molecular weight of the polyester polyol having an average number of functional groups of 2 and / or 3 is 250 or more, a coating film having a high elongation can be produced when used as a curing agent for a coating composition. When the number average molecular weight of the polyester polyol having an average number of functional groups of 2 and / or 3 is 4000 or less, the coating composition is easy to maintain a low viscosity state when used as a curing agent for a coating composition. The number average molecular weight of the polyester polyol having an average number of functional groups of 2 and / or 3 can be measured by the method described in the embodiments described later.
[0131] As the initiator, diols that can be used include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, trimethylpentanediol, cyclohexanediol, pentaerythritol, 2-hydroxymethylpropanediol, 2-ethyl-1,3-hexanediol, 1,3-propanediol, pentane-1,5-diol, heptane-1,7-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol, and the like. -diol, dodecane-1,12-diol, cyclohexane-1,4-diol, dipropylene glycol, propane-1,2-diol, butane-1,3-diol, hexane-1,2-diol, 2-methylpentane-2,4-diol, 3-methylpentane-1,5-diol, octane-1,2-diol, 2-butyl-2-ethylpropane-1,3-diol, decane-1,2-diol, etc.; triol: triethylene glycol, glycerol, etc. From the viewpoint of obtaining a polyisocyanate composition with a low viscosity, a polyol having a branched chain is preferred.
[0132] As the catalyst, it is preferred to use organic titanium compounds such as tetrabutyl titanate, tetrapropyl titanate, and tetraethyl titanate, tin compounds such as tin octoate, dibutyltin oxide, dibutyltin laurate, stannous chloride, and stannous bromide. From the viewpoint of easily adjusting the content of the polyester polyol having an average functional group number of 2, the catalyst is preferably a tin compound.
[0133] The ring-opening polymerization of ε-caprolactone and the like is preferably carried out by setting a molar ratio of ε-caprolactone and the above-mentioned initiator to a ratio of a predetermined molecular weight under a nitrogen atmosphere, adding a catalyst in an amount of 0.1 ppm to 100 ppm relative to ε-caprolactone, and reacting at a temperature of 150° C. to 200° C. for 4 hours to 10 hours. Among them, it is important to control the content of caprolactone dimers to a ratio of 100 ppm to 1000 ppm at the end of the reaction. If necessary, the caprolactone dimers can be removed from the generated polycaprolactone polyol by extraction, distillation, or the like.
[0134] In addition to ε-caprolactone, other cyclic lactones such as trimethylcaprolactone and valerolactone may be partially mixed.
[0135] The polyester polyol can be produced by subjecting a single dibasic acid or a mixture of dibasic acids to a single polyol or a mixture of polyols through a known condensation reaction, for example, by placing a dibasic acid component and a polyol component together and then heating them at about 160 to 220°C.
[0136] Examples of commercially available bifunctional polycaprolactone polyols include “PLACCEL210” (number average molecular weight 1000), “PLACCEL210CP” (number average molecular weight 1000), “PLACCEL212” (number average molecular weight 1250), “PLACCEL212CP” (number average molecular weight 1250), “PLACCEL220” (number average molecular weight 2000), “PLACCEL220CPB” (number average molecular weight 2000), and “PLACCEL220CPT” (number average molecular weight 2000), all manufactured by Daicel Corporation; and “Capa2043” (number average molecular weight 400), “Capa2054” (number average molecular weight 550), and “Capa2085” (number average molecular weight 830), all manufactured by Ingevity Corporation.
[0137] Examples of commercially available bifunctional polyester polyols include “Kuraray Polyol P-510” (number average molecular weight 500) manufactured by Kuraray Corporation and “ODX2406” (number average molecular weight 440) manufactured by DIC Corporation.
[0138] Examples of commercially available trifunctional polycaprolactone polyols include "PLACCEL305" (number average molecular weight 550), "PLACCEL308" (number average molecular weight 850), "PLACCEL309" (number average molecular weight 900), "PLACCEL312" (number average molecular weight 1250), and "PLACCEL320" (number average molecular weight 2000) manufactured by Daicel Corporation; "ODX2542C" (number average molecular weight 850) manufactured by DIC Corporation; and "Capa3050" (number average molecular weight 540) and "Capa23091" (number average molecular weight 900) manufactured by Ingevity Corporation.
[0139] (Polyoxyalkylene polyol)
[0140] The aforementioned polyalkylene polyol is a polyol containing -O(CH2) n -, the polyol having a valence of more than 2 and less than 4 can be derived from an alcohol having a valence of more than 2 and less than 4 and ethylene oxide, propylene oxide, tetrahydrofuran, etc. In addition, there is no particular limitation, for example, it can be obtained by cationic polymerization of ethylene oxide, propylene oxide, tetrahydrofuran, etc. with an alcohol having a valence of more than 2 and less than 4 as an initiator in the presence of a catalyst.
[0141] The number average molecular weight of the polyoxyalkylene polyol is preferably 200 or more and 2000 or less, more preferably 200 or more and 1500 or less, further preferably 200 or more and 1000 or less.
[0142] As the initiator, divalent alcohols such as ethylene glycol, propylene glycol, 1,3-butylene glycol, and neopentyl glycol, trivalent alcohols such as trimethylene glycol and glycerol, and tetravalent alcohols such as pentaerythritol can be used. From the viewpoint of obtaining a low-viscosity polyisocyanate component, branched polyols are preferred.
[0143] As the catalyst, a strong basic catalyst such as a hydroxide, an alcoholate, or an alkylamine of lithium, sodium, potassium, or the like can be used.
[0144] The cationic polymerization of ethylene oxide, propylene oxide, tetrahydrofuran, etc. is preferably carried out by setting the molar ratio of ethylene oxide, propylene oxide, tetrahydrofuran, etc. and the above-mentioned initiator to a ratio of a predetermined molecular weight under a nitrogen atmosphere, and then adding a catalyst in an amount of 0.1 ppm to 100 ppm relative to the ethylene oxide, propylene oxide, tetrahydrofuran, etc., and reacting at a temperature of 150° C. to 200° C. for 4 hours to 10 hours.
[0145] Examples of commercially available bifunctional polyoxyalkylene polyols include “ECOTRION H1000” (number average molecular weight 1000) and “ECOTRION H2000” (number average molecular weight 2000) manufactured by SK Chemicals, “Velvet H250” (number average molecular weight 227) manufactured by Allessa, and “BioPTMG650” (number average molecular weight 655) manufactured by Mitsubishi Chemical Corporation.
[0146] As the polyol component, it is preferred to contain two types of polyester polyols having different structures, or a polyester polyol and a polyoxyalkylene polyol. By making the polyol contain the above combination of two types of polyols, crystallization can be further suppressed.
[0147] The content of the polyester polyol when two polyester polyols having different structures are used in combination, or a polyester polyol and a polyoxyalkylene polyol, is preferably 20% by mass or more, more preferably 30% by mass or more, and further preferably 35% by mass or more relative to the total mass of the polyol. By making the content of the polyester polyol above the above lower limit, the weather resistance when the coating film is made can be made better.
[0148] The polyisocyanate compositions (C-1) and (C-2) contain a carbamate group and an allophanate group in one molecule. The carbamate group is formed by the reaction of an isocyanate group of a diisocyanate with a hydroxyl group of a polyol. In addition, the allophanate group is formed by the reaction of a carbamate group with an isocyanate group of a diisocyanate, or by the reaction of two isocyanate groups of a diisocyanate with one hydroxyl group of a polyol.
[0149] The molar ratio of the carbamate group / alophanate group of the polyisocyanate compositions (C-1) and (C-2) is 100 / 0 to 75 / 25. The molar ratio of the carbamate group / alophanate group is preferably 100 / 0 to 80 / 20, more preferably 100 / 0 to 85 / 15, further preferably 100 / 0 to 90 / 10, and particularly preferably 99 / 1 to 90 / 10. By being within the above range, the storage stability of the obtained polyisocyanate composition becomes high, and the matting property of the obtained coating film and the elongation at a low temperature of about -20°C can be taken into account within a suitable range.
[0150] The polyisocyanate compositions (C-1) and (C-2) may have other functional groups such as an isocyanurate group and a uretdione group in addition to the urethane group and the allophanate group.
[0151] Alternatively, the polyisocyanate compositions (C-1) and (C-2) of the present embodiment may contain, in addition to the polyisocyanate having a carbamate group and an allophanate group in the molecule, a polyisocyanate having any one of the functional groups of a carbamate group and an allophanate group, a polyisocyanate having other functional groups such as an isocyanurate group and a uretdione group alone, or a polyisocyanate having two or more of these other functional groups in combination.
[0152] The molar amount of each functional group in the polyisocyanate compositions (C-1) and (C-2) can be determined, for example, by 13 The ratio of the molar amount of the above-mentioned specific functional groups can be calculated using the calculated molar amount of each functional group measured by C-NMR spectroscopy.
[0153] (Polyisocyanate component (C-3))
[0154] The polyisocyanate composition (C) used in the present embodiment may further include a polyisocyanate component (C-3), wherein the polyisocyanate component (C-3) is obtained from at least one diisocyanate selected from aliphatic diisocyanates and alicyclic diisocyanates and a monohydric alcohol having a carbon number of 1 to 20, and the molar ratio of the allophanate group to the isocyanurate group (allophonate group / isocyanurate group) of the polyisocyanate component (C-3) is 100 / 0 to 70 / 30.
[0155] The carbon number of the monohydric alcohol having 1 to 20 in the polyisocyanate component (C-3) is preferably 2 or more, more preferably 3 or more, particularly preferably 4 or more, and most preferably 6 or more. The carbon number of the monohydric alcohol having 1 to 20 is preferably 16 or less, more preferably 12 or less, and particularly preferably 9 or less. The monohydric alcohol may be used alone or in combination of two or more. In addition, the monohydric alcohol used in the present invention may contain an ether group, an ester group, or a carboxyl group in the molecule, and is preferably a monohydric alcohol containing a saturated hydrocarbon group. In addition, a monohydric alcohol having a branched chain is more preferred.
[0156] Examples of such monohydric alcohols include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, 1-pentanol, 2-pentanol, isopentanol, 1-hexanol, 2-hexanol, 1-heptanol, 1-octanol, 2-ethyl-1-hexanol, 3,3,5-trimethyl-1-hexanol, tridecanol, pentadecanol, palmityl alcohol, stearyl alcohol, cyclopentanol, cyclohexanol, methylcyclohexanol, and trimethylcyclohexanol.
[0157] Among them, isobutyl alcohol, n-butyl alcohol, isopentanol, 1-hexanol, 1-heptanol, 1-octanol, 2-ethyl-1-hexanol, tridecyl alcohol, pentadecanol, palmityl alcohol, stearyl alcohol, and 1,3,5-trimethylcyclohexanol are more preferred.
[0158] More preferred are 1-propanol, isobutyl alcohol, 1-butanol, isopentanol, pentanol, 1-hexanol, 2-hexanol, 1-heptanol, 1-octanol, 2-octanol, 2-ethyl-hexanol, and 3,3,5-trimethyl-1-hexanol.
[0159] Most preferred are 1-hexanol, 2-hexanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, and 3,3,5-trimethyl-1-hexanol.
[0160] In the above-mentioned polyisocyanate component (C-3), the molar ratio of allophanate group / isocyanurate group is 100 / 0 to 70 / 30, preferably 100 / 0 to 80 / 20. The molar ratio of allophanate group / isocyanurate group is preferably 99 / 1 or less, and more preferably 98 / 2 or less. The molar ratio of allophanate group / isocyanurate group is preferably 85 / 15 or more, more preferably 90 / 10 or more, and particularly preferably 95 / 5 or more. When the molar ratio of allophanate group to isocyanurate group is 100 / 0 to 70 / 30, the curing property becomes sufficient.
[0161] The content of the polyisocyanate component (C-3) contained in the polyisocyanate composition (C) is preferably 0% to 50%, more preferably 0% to 30%, and even more preferably 0% to 20%. By being within the above range, crystallization can be further suppressed, and the polyisocyanate composition of the present embodiment can be mixed with a coating composition, particularly a polyaspartic acid coating composition, as a uniform curing agent. Thus, a coating film with better curability and surface appearance can be obtained.
[0162] The polyisocyanate composition (C) used in the present embodiment can be manufactured by the method described in the International Publication No. 2018 / 163959. Specifically, the polyisocyanate composition used in the present embodiment can be obtained as follows: in the presence of an excess of diisocyanate monomer, the isocyanate group of the diisocyanate monomer is reacted with a polyester polyol having an average functional group number of 2 and / or 3, and / or a hydroxyl group of a polyoxyalkylene polyol having an average functional group number of 2 to 4, and a carbamate reaction is performed to form a carbamate group, and then the unreacted diisocyanate monomer is removed to obtain. Furthermore, an allophanate reaction can also be performed after the carbamate reaction or simultaneously with the carbamate reaction. The allophanate reaction can also be performed by heating alone, but it can also be performed using an allophanate reaction catalyst.
[0163] The isocyanate content (hereinafter also referred to as "NCO content") of the polyisocyanate composition (C) used in the present embodiment is preferably 5% by mass or more and 30% by mass or less relative to the total amount (100% by mass) of the polyisocyanate composition. The NCO content is more preferably 6% by mass or more, and further preferably 7% by mass or more. The NCO content is more preferably 25% by mass or less, and further preferably 20% by mass or less. When the NCO content is 5% by mass or more, it is easier to maintain the drying and curing properties of the coating film. When the NCO content is 30% by mass or less, when used as a curing agent for a coating composition, it is easy to improve the elongation, scratch resistance and weather resistance of the obtained coating film at a low temperature of about -20°C. The NCO content of the polyisocyanate composition can be determined by the method described in the examples described later.
[0164] The viscosity of the polyisocyanate composition (C) used in the present embodiment at 25°C is preferably 500 mPa.s or more and 10000 mPa.s or less. The viscosity is more preferably 600 mPa.s or more, further preferably 700 mPa.s or more, and particularly preferably 800 mPa.s or more. The viscosity is more preferably 5000 mPa.s or less, further preferably 3000 mPa.s or less, and particularly preferably 2000 mPa.s or less. When the viscosity is 500 mPa.s or more, when used as a curing agent for a coating composition, it is easy to improve the elongation and scratch resistance of the obtained coating film at a low temperature of about -20°C. When the viscosity is 10000 mPa.s or less, it is easier to maintain dryness. The viscosity of the polyisocyanate composition can be measured by the method described in the examples described later.
[0165] The number average molecular weight of the polyisocyanate composition (C) used in the present embodiment is preferably 250 or more and 4000 or less. The number average molecular weight is preferably 300 or more and 3000 or less, more preferably 300 or more and 2500 or less, and further preferably 400 or more and 2000 or less. By making the number average molecular weight 250 or more, when used as a curing agent for a coating composition, it is easy to improve the elongation, scratch resistance and weather resistance of the obtained coating film at a low temperature of about -20°C. By making the number average molecular weight 4000 or less, it is easier to maintain dryness. The number average molecular weight of the polyisocyanate composition can be measured by the method described in the examples described later.
[0166] The average number of isocyanate groups of the polyisocyanate composition (C) used in the present embodiment is preferably 2.0 or more and 10.0 or less. The average number of isocyanate groups is more preferably 2.1 or more, further preferably 2.2 or more, and particularly preferably 2.3 or more. The average number of isocyanate groups is preferably 8.0 or less, more preferably 6.0 or less, and particularly preferably 4.0 or less. By making the average number of isocyanate groups 2.0 or more, it is easier to maintain dryness. By making the average number of isocyanate groups 10.0 or less, when used as a curing agent for a coating composition, it is easy to improve the elongation, scratch resistance and weather resistance of the obtained coating film at a low temperature of about -20°C. The average number of isocyanate groups of the polyisocyanate composition can be determined by the method described in the examples described later.
[0167] The mass concentration of the diisocyanate monomer in the polyisocyanate composition (C) used in the present embodiment is preferably 1.0 mass % or less, more preferably 0.5 mass % or less, further preferably 0.3 mass % or less, particularly preferably 0.1 mass % or less, relative to the total amount (100 mass %) of the polyisocyanate composition.
[0168] By setting the mass concentration of the diisocyanate monomer to 1.0 mass % or less, it is easier to maintain the dryness. The mass concentration of the diisocyanate monomer in the polyisocyanate composition can be measured by the method described in Examples described below.
[0169] (Isocyanate / Amino)
[0170] The molar ratio of the isocyanate group of the polyisocyanate composition (C) to the amino group of the aspartic acid ester compound (A-1) (isocyanate group / amino group) is preferably 1 / 10 or more and 10 / 1 or less, more preferably 1 / 5 or more and 5 / 1 or less, and further preferably 1 / 2 or more and 2 / 1 or less. By making the isocyanate group / amino group 1 / 10 or more, the main agent will not become excessive, and the elongation at a low temperature of about -20°C when the coating is made can be good. In addition, by making the isocyanate group / amino group within the above numerical range, the balance of the isocyanate group and the amino group is maintained well, the concentration of the urea bond that becomes the bonding point in the coating can be further increased, and the weather resistance when the coating is made can be good.
[0171] (isocyanate / hydroxyl)
[0172] The molar ratio of the isocyanate group of the polyisocyanate composition (C) to the hydroxyl group of the hydroxyl-containing resin compound (A-2) (isocyanate group / hydroxyl group) is preferably 1 / 10 or more and 10 / 1 or less, more preferably 1 / 5 or more and 5 / 1 or less, and further preferably 1 / 2 or more and 2 / 1 or less. By making the isocyanate group / hydroxyl group 1 / 10 or more, the main agent will not become excessive, and the elongation at a low temperature of about -20°C when the coating is made can be good. In addition, by making the isocyanate group / hydroxyl group within the above numerical range, the balance of the isocyanate group and the hydroxyl group is maintained well, the concentration of the urethane bond that serves as the bonding point in the coating can be further increased, and the weather resistance when the coating is made can be good.
[0173] (Other ingredients)
[0174] The coating composition of the present embodiment can further include other main components such as melamine resin, epoxy resin, polyurethane resin as needed. In addition, when the above-mentioned hydroxyl-containing (water-based) resin compound has a carboxyl group, a compound containing an oxazoline group and a compound containing a carbodiimide group can be mixed. In addition, when the above-mentioned hydroxyl-containing (water-based) resin compound has a carbonyl group, a compound containing a hydrazide group and a compound containing a semicarbazide group can be mixed. These compounds can be mixed alone, or more than two kinds can be mixed in combination.
[0175] From the aspect of making the appearance when the coating film is made more excellent, the coating composition of the present embodiment can suitably add known components as the compounding agent of the coating composition. As such components, for example, solvents, surfactants, photosensitizers, foam stabilizers, foaming agents (foaming agents), foaming aids, foam stabilizers, defoamers (foam suppressants, foam breakers), emulsifiers, pigment dispersants, lubricants, propellants, thickeners, curing agents, polymerization initiators, pigments, plasticizers, adhesives, fillers, antifouling agents, rust inhibitors, slip agents, desiccants, stabilizers, ultraviolet absorbers, antibacterial or antifungal agents, flame retardants, etc. can be listed.
[0176] <Method for producing coating composition>
[0177] The coating composition of the present embodiment is obtained as follows: a matting agent (B) is added to any one or both of the above-mentioned aspartic acid ester compound (A-1) and the hydroxyl-containing resin compound (A-2) while mixing, and then other components are mixed as needed to obtain a main agent (MC), and the above-mentioned polyisocyanate composition (C) as a curing agent component is mixed in the main agent (MC), and mixed using a known method to obtain. At this time, a solvent may be used, or no solvent may be used. The coating composition of the present embodiment has a lower viscosity than in the past, so even a high-solid formulation can be manufactured while maintaining operability.
[0178] <Purpose>
[0179] The coating composition of this embodiment is suitably used as a primer, mid-coat, or top-coat on metals such as steel plates and surface-treated steel plates, plastics, inorganic materials such as ceramics, glass, and concrete by roller coating, curtain flow coating, spray coating, electrostatic coating, bell coating, dipping, roller coating, brush coating, etc.
[0180] The coating composition of the present embodiment is suitably used in pre-coated metals including rust-proof steel sheets, automobile coating parts, plastic coating parts, etc., in order to impart aesthetics, weather resistance, acid resistance, rust resistance, peeling resistance, adhesion, etc. In addition, the coating composition of the present embodiment is also useful as an adhesive, a binder, an elastomer, a foam, a surface treatment agent, etc.
[0181] In addition, the coating film of the coating composition of the present embodiment is softened, the crosslinking density of the coating film is improved, and the weather resistance is particularly excellent. Therefore, the coating composition of the present embodiment is suitable for heavy-duty anti-corrosion coating of structures that require long-term weather resistance, such as bridges, highways, transmission towers, wind power generation facilities (towers, blades, etc.) exposed to harsh environments such as wind, rain, snow, cold and hot temperature differences.
[0182] <Coating>
[0183] The coating film of the present embodiment is a coating film formed by curing the above-mentioned coating composition.
[0184] The coating film of this embodiment has an excellent matte appearance and good chemical resistance.
[0185] The coating film of the present embodiment can be obtained by applying the coating composition by a known method such as roller coating, curtain flow coating, spray coating, bell coating, electrostatic coating, etc., and curing the coating composition through a room temperature drying or baking step.
[0186] <Main agent for paint>
[0187] The present embodiment is a main agent for coating materials, comprising one or both of an aspartic acid ester compound (A-1) and a hydroxyl group-containing resin compound (A-2), and organic polymer hollow particles (B-3).
[0188] Hereinafter, “either or both of the aspartic acid ester compound (A-1) and the hydroxyl group-containing resin compound (A-2)” may be referred to as “main agent component”.
[0189] Hereinafter, each component constituting the main agent for coating material according to the present embodiment will be described.
[0190] Main ingredients
[0191] The description of the main agent component is the same as that described in the above (aspartic acid ester compound (A-1)) and the above (hydroxyl-containing resin compound (A-2)).
[0192] 《Organic polymer hollow particles (B-3)》
[0193] The description of the organic polymer hollow particles (B-3) contained in the coating material base is the same as that described in the above (Organic polymer hollow particles (B-3)).
[0194] In the coating main agent of the present embodiment, the content of the organic polymer hollow particles (B-3) is 10% by weight or more and 200% by weight or less, preferably 15% by weight or more and 150% by weight or less, more preferably 25% by weight or more and 130% by weight or less, relative to the total amount of the main agent component. By making the content within the above range, the viscosity of the coating and the matte property of the coating film can be taken into account within a suitable range.
[0195] The solid content concentration of the main agent for coating material of the present embodiment is 70% by weight or more.
[0196] When the solid content concentration is 70% by weight or more, both excellent matte appearance and suppression of the viscosity increase of the coating can be achieved. In addition, the coating composition containing the above-mentioned coating main agent has good appearance and chemical resistance when formed into a coating film.
[0197] 《Coating composition 2》
[0198] The coating composition 2 which is one embodiment of the present invention comprises the above-mentioned coating main agent and the polyisocyanate composition (C1). The solid content concentration of the coating composition 2 is 70% by weight or more.
[0199] 《Polyisocyanate composition (C1)》
[0200] As the polyisocyanate composition (C1) used in the present embodiment, there can be cited a polyisocyanate component obtained from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates and a polyester polyol having an average functional group number of 2 and / or 3. In addition, the polyisocyanate composition (C1) can be a polyisocyanate component that can be obtained as follows: using a known method using one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates as a raw material, performing one or more reactions selected from the group consisting of biuret reaction, isocyanurate reaction, urethanization reaction, allophanate reaction, iminooxadiazinedionization reaction, uretdione reaction, and uretonimidization reaction, temporarily producing in the presence of an excess of diisocyanate monomers, and removing unreacted diisocyanate monomers after the reaction is completed, thereby obtaining.
[0201] ·Diisocyanate
[0202] The diisocyanate used as a raw material of the polyisocyanate contained in the polyisocyanate composition (C1) used in the present embodiment is one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates.
[0203] The aliphatic diisocyanate used in the present embodiment is not particularly limited, and is preferably an aliphatic diisocyanate having a carbon number of 4 or more and 30 or less, for example, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate (hereinafter, abbreviated as "HDI"), 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, and lysine diisocyanate. Among them, HDI is more preferred from the ease of industrial acquisition. The aliphatic diisocyanate shown above can be used alone or in combination of two or more.
[0204] The alicyclic diisocyanate used in the present embodiment is not particularly limited, and is preferably an alicyclic diisocyanate having a carbon number of 8 or more and 30 or less, for example, isophorone diisocyanate (hereinafter, abbreviated as "IPDI"), 1,3-bis (isocyanatomethyl) -cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, norbornene diisocyanate, and hydrogenated xylylene diisocyanate. Among them, IPDI is more preferred from the perspective of weather resistance and ease of industrial acquisition. The alicyclic diisocyanate shown above can be used alone or in combination of two or more.
[0205] As the diisocyanate monomer, one or two or more aliphatic diisocyanates and one or two or more alicyclic diisocyanates may be used in combination.
[0206] The polyisocyanate composition (C1) used in the present embodiment may further contain a polyisocyanate component obtained from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates and a polyoxyalkylene polyol having an average functional group number of 2 to 4.
[0207] The polyisocyanate composition (C1) used in the present embodiment can be produced by the method described in International Publication No. 2018 / 163953 and International Publication No. 2018 / 163959.
[0208] Matting Agent
[0209] The coating composition 2 of this embodiment may further include a matting agent in addition to the above-mentioned organic polymer hollow particles (B-3). The matting agent is not particularly limited, and examples thereof include dry silica, precipitated silica, organic polymer microparticles, polyethylene wax, etc., which are different from the above-mentioned organic polymer hollow particles (B-3).
[0210] The coating composition 2 may contain the above-mentioned (other components) as necessary.
[0211] <Method for producing coating composition 2>
[0212] The coating composition 2 of the present embodiment is obtained as follows: the organic polymer hollow particles (B-3) are added to the above-mentioned main agent component while mixing, and then other components are mixed as needed to obtain a main agent for coating (MC), and the above-mentioned polyisocyanate composition (C1) as a curing agent component is added to the main agent for coating (MC), and mixed using a known method to obtain. At this time, a solvent may be used, or no solvent may be used.
[0213] The coating composition 2 of the present embodiment has a lower viscosity than conventional ones, and therefore can be produced while maintaining workability even in a high-solid formulation.
[0214] <Curing agent for paint>
[0215] One embodiment of the present invention is a coating material curing agent comprising a polyisocyanate composition (C1) and organic polymer hollow particles (B-3).
[0216] Regarding the coating curing agent, the content ratio of the organic polymer hollow particles (B-3) is 10% by weight or more and 200% by weight or less, more preferably 25% by weight or more and 130% by weight or less, relative to the total amount of the polyisocyanate composition (C1). By making the content within the above range, the viscosity of the coating composition and the matte property of the coating film can be taken into account within a suitable range.
[0217] The solid content concentration of the coating material curing agent is 70% by weight or more.
[0218] The coating composition 2 of the present embodiment can be produced by preparing a coating curing agent and mixing the coating curing agent with the above-mentioned main agent component.
[0219] When preparing the curing agent for coating materials, in addition to the polyisocyanate composition (C1) and the organic polymer hollow particles (B-3), the above-mentioned (other components) may be blended as necessary.
[0220] When the coating material curing agent is mixed with the above-mentioned main component, the above-mentioned (other components) may be blended as necessary.
[0221] The preparation of the coating curing agent or the mixing of the coating curing agent with the main agent component may be carried out by a known mixing method. In this case, a solvent may be used or not.
[0222] <Purpose>
[0223] The application of the coating composition 2 is the same as the method described in the above <Application>.
[0224] 《Coating》
[0225] One embodiment of the present invention is a coating film formed by curing the coating composition 2. The description of the coating film formed by curing the coating composition 2 is the same as the method described in the above <Coating film>.
[0226] <Method of giving a matte appearance>
[0227] One embodiment of the present invention is a method for imparting a matte appearance to a cured product of a coating composition 2, wherein organic polymer hollow particles (B-3) are added as a matte agent to the coating composition 2 comprising a main component and a polyisocyanate composition (C1).
[0228] Example
[0229] Hereinafter, the present embodiment will be described in more detail with reference to Examples, but the present embodiment is not limited to these Examples.
[0230] The following describes the methods for measuring various physical properties and the methods for evaluating various properties. It should be noted that, unless otherwise specified, "parts" and "%" mean "parts by mass" and "mass %".
[0231] Details of materials used in Examples are as follows.
[0232] Aspartic acid ester compound (A-1):
[0233] Trade name: "FEISPARTIC F-420" (manufactured by Shenzhen Feiyang Protech Co., Ltd.), solid content concentration 97%, amine value 201
[0234] Trade name: FEISPARTIC F-520 (manufactured by Shenzhen Feiyang Protech Co., Ltd.), solid content concentration: 97%, amine value: 191
[0235] Hydroxyl-containing resin compound (A-2):
[0236] Trade name: "ACRYDIC WGU-337" (manufactured by DIC Corporation), solid content concentration 69%, hydroxyl value 117
[0237] Inorganic particles (B-1):
[0238] Precipitated silica, trade name "ACEMATT HK400" (manufactured by Evonik Japan Co., Ltd.), average particle size 6.3 μm, untreated
[0239] Precipitated silica, trade name "ACEMATT OK412" (manufactured by Evonik Japan Co., Ltd.), average particle size 6.3 μm, treated with polyethylene wax
[0240] Organic polymer microparticles (B-2):
[0241] Trade name: "TAFTIC AR650S" (manufactured by Japan Exlan Co., Ltd.), average particle size = 20 μm
[0242] Trade name: "TAFTIC AR650MZ" (manufactured by Exlan Japan Co., Ltd.), average particle size = 60 μm
[0243] Organic polymer hollow particles (B-3):
[0244] Trade name: "Matsumoto Microsphere MFL-81GTA" (manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd.), average particle size = 20 μm
[0245] Trade name: "Matsumoto Microsphere MFL-HD60CA" (Matsumoto Oil & Fats Pharmaceutical Co., Ltd.), average particle size = 61 μm
[0246] Wax particles (B-4):
[0247] Trade name: CERAFLOUR913 (manufactured by BYK-Chemie), average particle size = 18 μm
[0248] Pigment: Titanium oxide, trade name "TIPAQUE CR-97" (manufactured by Ishihara Sangyo Co., Ltd.)
[0249] Anti-settling agent: organic bentonite, trade name "Bentone SD-2" (manufactured by Elementis)
[0250] Dehydrating agent: Trade name Molecular Sieve 3A (manufactured by Union Showa Co., Ltd.)
[0251] Ultraviolet light absorber: Trade name: TINUVIN-1130 (manufactured by BASF)
[0252] Light stabilizer: Trade name TINUVIN-292 (manufactured by BASF)
[0253] Dispersant: Trade name BYK-163 (manufactured by BYK)
[0254] Defoamer: Trade name BYK-141 (manufactured by BYK)
[0255] Surface conditioner: BYK-331 (manufactured by BYK)
[0256] Solvent: Butyl acetate
[0257] <Measurement Methods of Physical Properties>
[0258] [Physical properties 1]
[0259] (Measurement of average particle size of matting agent (B))
[0260] As a measuring device, the particle size distribution was measured by a dry method using a laser diffraction particle size analyzer (Mastersizer 3000) manufactured by Malvern. The average particle size was measured using a D50 value measured on a volume basis.
[0261] [Physical Property 2] Molar Ratio of Carbamate Group / Allophanate Group
[0262] By using Biospin Avance600 (trade name) manufactured by Bruker 13 The molar ratio of urethane group / allophanate group was determined by C-NMR measurement.
[0263] Specific measurement conditions are as follows.
[0264] 13 C-NMR apparatus: AVANCE600 (manufactured by Bruker)
[0265] Cryoprobe (Bruker)
[0266] Cryo Probe
[0267] CPDUL
[0268] 600S3-C / HD-05Z
[0269] Resonance frequency: 150MHz
[0270] Concentration: 60wt / vol%
[0271] Displacement standard: CDCl3 (77ppm)
[0272] Cumulative times: 10,000 times
[0273] Pulse program: zgpg30 (proton complete decoupling method, waiting time 2 seconds)
[0274] The integrated value of the following signal was divided by the number of carbon atoms measured to determine the molar ratio of the urethane group / allophanate group.
[0275] Molar amount of carbamate group (mol%): 156.5 ppm Approximately: integral value ÷ 1
[0276] Molar amount of allophanate group (mol %): around 154 ppm: integrated value ÷ 1
[0277] [Physical Properties 3]
[0278] (NCO content (mass %))
[0279] The NCO content (isocyanate content, mass %) of the polyisocyanate composition is measured as follows. Accurately weigh more than 1g and less than 3g (Wg) of the polyisocyanate composition manufactured by the manufacturing example in a conical flask, and then add 20mL of toluene to completely dissolve the polyisocyanate composition. Thereafter, add 10mL of a 2N toluene solution of di-n-butylamine, mix thoroughly, and leave at room temperature for 15 minutes. Furthermore, add 70mL of isopropanol to the solution and mix thoroughly. Using an indicator, the solution is titrated with 1N hydrochloric acid solution (factor F) to obtain a titration value V2mL. For the same titration operation, the titration value V1mL is obtained without using polyisocyanates. According to the titration value V2mL and the titration value V1mL obtained, the NCO content (mass %) of the polyisocyanate is calculated based on the following formula.
[0280] (NCO content (mass %)) = (V1-V2) × F × 42 / (W × 1000) × 100
[0281] [Physical Properties 4]
[0282] (Viscosity of polyisocyanate composition (mPa.s))
[0283] The viscosity of the polyisocyanate composition was measured at 25° C. using an E-type viscometer (trade name: RE-85R, manufactured by Toki Sangyo Co., Ltd.). A standard rotor (1°34′×R24) was used for the measurement. The rotation speed was set as follows.
[0284] (Speed)
[0285] 100r.pm (less than 128mPa·s)
[0286] 50r.pm (128mPa·s or more and less than 256mPa·s)
[0287] 20r.pm (256mPa·s or more and less than 640mPa·s)
[0288] 10r.pm (640mPa·s or more and less than 1280mPa·s)
[0289] 5r.pm (1280mPa·s or more and less than 2560mPa·s)
[0290] 2.5rpm (2560mPa·s or more and less than 5120mPa·s)
[0291] 1.0rpm (5184mPa.s or more and less than 12960mPa.s)
[0292] [Physical Properties 5]
[0293] (Crystallinity of polyisocyanate composition)
[0294] The turbidity of the polyisocyanate composition at room temperature (23° C.) was measured as transmittance (%) at 550 nm in UV measurement using JASCO V-650. The measured transmittance was evaluated according to the following evaluation criteria.
[0295] (Evaluation Criteria)
[0296] A: The transmittance at 550nm is more than 70%
[0297] B: Transmittance at 550nm is less than 70%
[0298] [Physical Properties 6]
[0299] (Number average molecular weight)
[0300] The number average molecular weight of the polyisocyanate composition is determined as a polystyrene-based number average molecular weight measured by gel permeation chromatography (hereinafter, abbreviated as “GPC”) using the following apparatus.
[0301] Device: "HLC-8120GPC" (trade name) manufactured by Tosoh Corporation
[0302] Column: "TSKgel SuperH1000" (trade name) manufactured by Tosoh Corporation × 1
[0303] "TSKgel SuperH2000" (trade name) × 1 piece
[0304] "TSKgel SuperH3000" (trade name) × 1 piece
[0305] Carrier: Tetrahydrofuran
[0306] Detection method: Differential refractometer
[0307] [Properties 7]
[0308] Average number of isocyanate groups
[0309] The average number of isocyanate groups in the polyisocyanate composition is calculated from [Physical Property 1] NCO content and [Physical Property 3] number average molecular weight based on the following formula.
[0310] Average number of isocyanate groups = number average molecular weight × NCO content / 100 / 42
[0311] [Property 8]
[0312] Diisocyanate monomer mass concentration (mass %)
[0313] The mass concentration of diisocyanate in the polyisocyanate composition is determined as follows. Initially, place a 20 mL sample bottle on a digital balance and accurately weigh about 1 g of the sample. Then, add 0.03 to 0.04 g of nitrobenzene (internal standard solution) and weigh accurately. Finally, add about 9 mL of ethyl acetate, cover tightly and mix thoroughly to prepare the sample. Perform gas chromatography analysis on the prepared sample under the following conditions for quantitative analysis.
[0314] Device: GC-8A manufactured by Shimadzu
[0315] Column: "Silicone OV-17" manufactured by Shinwa Chemical Co., Ltd.
[0316] Column oven temperature: 120°C
[0317] Injection / detector temperature: 160°C
[0318] [Properties 9]
[0319] (Main component (MC) viscosity (mPa.s))
[0320] The viscosity of the obtained main component (MC) was measured at 25° C. using an E-type viscometer (trade name: RE-85R or RE-85U, manufactured by Toki Sangyo Co., Ltd.) using a standard rotor (RE-85R: 1°34′×R24, RE-85U: 3°×R14). The rotation speed was set as follows.
[0321] (Speed: RE-85R)
[0322] 100r.pm (less than 128mPa·s)
[0323] 50r.pm (128mPa·s or more and less than 256mPa·s)
[0324] 20r.pm (256mPa·s or more and less than 640mPa·s)
[0325] 10r.pm (640mPa·s or more and less than 1280mPa·s)
[0326] 5r.pm (1280mPa·s or more and less than 2560mPa·s)
[0327] 2.5rpm (2560mPa·s or more and less than 5120mPa·s)
[0328] (Speed: RE-85U)
[0329] 100r.pm (less than 5002mPa·s)
[0330] 50r.pm (5002mPa·s or more and less than 10.0Pa·s)
[0331] 20r.pm (10.0Pa·s or more and less than 25.01Pa·s)
[0332] 10r.pm (25.01Pa·s or more and less than 50.02Pa·s)
[0333] 5r.pm (50.02Pa·s or more and less than 100.0Pa·s)
[0334] 2.5rpm (100.0Pa·s or more and less than 200.1Pa·s)
[0335] (Evaluation Criteria)
[0336] S: 5000mPa·s or less
[0337] A: 5001mPa·s or more and less than 20000mPa·s (20.0Pa·s)
[0338] B: 20001mPa·s (20.0Pa·s) or more
[0339] [Properties 10]
[0340] (Solid content concentration (%) of coating composition (P))
[0341] After accurately weighing an aluminum pan with a bottom diameter of 38 mm, about 1 g of the coating composition (P) of the embodiment or comparative example was placed on the aluminum pan and accurately weighed (W1), and after adjusting to a uniform thickness, it was kept in an oven at 105° C. for 3 hours. After the aluminum pan reached room temperature, the coating composition remaining in the aluminum pan was accurately weighed (W2). Then, the obtained W1 and W2 were substituted into the following formula to calculate the solid content concentration (%) of the coating composition.
[0342] (Solid content concentration (%) of coating composition (P) = W2 / W1×100
[0343] <Evaluation method of coating film>
[0344] [Evaluation 1]
[0345] (Appearance of coating film)
[0346] The coating composition (P) obtained in the examples and comparative examples was applied to a glass plate with an applicator to a dry film thickness of 40 μm or more and 60 μm or less. After coating, it was cured for 7 days under the conditions of 23° C. and 50% humidity to obtain each coating film. The appearance of each coating film was evaluated according to the following evaluation criteria.
[0347] (Evaluation Criteria)
[0348] S: The surface is very smooth and no bumps can be seen.
[0349] A: The surface is smooth, but a few small bumps can be seen.
[0350] B: There are many bumps and wrinkles on the surface.
[0351] [Evaluation 2]
[0352] (Extinction efficiency (ME) of matting agent (B))
[0353] The matting efficiency (ME) of the matting agent (B) is calculated by the following method.
[0354] The coating composition (P) obtained in the examples and comparative examples was applied to a glass plate with an applicator to a dry film thickness of 40 μm or more and 60 μm or less. After coating, it was cured for 7 days at 23° C. and 50% humidity to obtain each coating film. Next, the gloss value of the coating film was measured at 60 degrees -60 degrees using a gloss meter (Haze-Gloss, manufactured by BYK-Garner) to obtain a gloss value (G1).
[0355] The obtained gloss value (G1), the gloss value of the full gloss coating film (coating film not containing a matting agent) (G0=95), and the content of the matting agent (Bw (weight %): the content of the matting agent (B) in the obtained coating composition relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2), and the polyisocyanate composition (C)) were substituted into the following formula to calculate the matting efficiency (ME) of the matting agent (B), and the evaluation was performed according to the following evaluation criteria.
[0356] (Extinction efficiency (ME) of matting agent (B)) = (G0-G1) / Bw
[0357] (Evaluation Criteria)
[0358] S: Extinction efficiency (ME) is 4 or more, and the extinction property is better
[0359] A: Extinction efficiency (ME) is 2 or more and less than 4, and the extinction property is good
[0360] B: Extinction efficiency (ME) is less than 2, and the extinction property is insufficient
[0361] [Evaluation 3]
[0362] (Low-temperature elongation of coating film)
[0363] The coating composition (P) obtained in the embodiment and the comparative example was applied to a polypropylene (PP) plate with an applicator in a manner such that the dry film thickness was 80 μm or more and 100 μm or less. After coating, each coating film was cured for 7 days at 23°C and 50% humidity. The elongation of the coating film was measured at a temperature of -20°C using a tensile tester (RTE-1210 made by Orientec) and a thermostatic bath (TLA-R3T-FW made by Orientec) at a tensile speed of 20 mm / min and a gripping interval of 20 mm. The low-temperature elongation of each coating film was evaluated according to the evaluation criteria shown below.
[0364] (Evaluation Criteria)
[0365] S: coating elongation is more than 30%
[0366] A: The coating elongation is 10% or more and less than 30%
[0367] B: coating elongation is less than 10%
[0368] <Manufacturing of Main Component (MC)>
[0369] [Production Example 1]
[0370] 33.5 parts of FEISPARTIC F-420 as an aspartic acid ester compound (A-1), 36.9 parts of TIPAQUE CR-97 as a pigment, 2.3 parts of BYK-163 as an additive, 0.35 parts of BYK-141, 1.8 parts of Bentone SD2, 3.5 parts of Molecular Sieve 3A, and 21 parts of butyl acetate as a solvent were placed in a metal container, and then stirred and mixed with a disperser to obtain a mixture. Next, the entire amount of the obtained mixture and glass beads (equivalent to the total mass of the mixture) were added to a disperser (manufactured by Taihei Systems Co., Ltd., tabletop SG MILL 1500W model) to disperse the pigment until the particle size of the pigment reached 20 μm or less, thereby preparing a pigment dispersion paint. Furthermore, 19 parts of ACEMATT HK400 as a matting agent (B), 1.1 parts of TINUVIN-1130 as an additive, 0.70 parts of TINUVIN-292, 0.12 parts of BYK-331, and 18 parts of butyl acetate as a solvent were added to 99.4 parts of the obtained pigment dispersion paint, and the mixture was stirred and mixed until uniform using a disperser to obtain a main agent (mc-1).
[0371] [Production Examples 2 to 7]
[0372] Main agents (mc-2) to (mc-7) were obtained in the same manner as in [Production Example 1] except that the materials listed in Table 1 were used as the matting agent (B).
[0373] [Production Example 8]
[0374] A base compound (mc-8) was obtained in the same manner as in [Production Example 1] except that the materials listed in Table 1 were used as the aspartic acid ester compound (A-1).
[0375] [Production Example 9]
[0376] A main agent (mc-9) was obtained in the same manner as in [Production Example 1] except that the materials listed in Table 1 were used as the hydroxyl-containing resin compound (A-2) instead of the aspartic acid ester compound (A-1).
[0377] [Production Examples 10 to 12]
[0378] Except having changed the compounding amount of a material as described in Table 1, it carried out similarly to [Production Example 2], and obtained the main agent (mc-10) - (mc-12).
[0379] [Table 1]
[0380]
[0381] [Comparative Production Example 1]
[0382] A main component (mc-13) was obtained in the same manner as in [Production Example 2] except that the types and blending amounts of the materials were changed as described in Table 2.
[0383] [Table 2]
[0384]
[0385] <Production of Polyisocyanate Composition (C)>
[0386] [Synthesis example 1]
[0387] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was placed in a nitrogen atmosphere, 100 parts of HDI and 33.2 parts of Capa2054 (manufactured by Ingevity; number average molecular weight 550, hydroxyl value 204, number of functional groups 2) as a polycaprolactone polyol were added, and the temperature in the reactor was maintained at 100°C for 2 hours under stirring to carry out a urethane reaction. After filtering the cooled reaction solution, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (c-1) having an NCO content of 9.1% by mass, a viscosity of 1460 mPa.s at 25°C, a number average molecular weight of 1520, an average number of isocyanate groups of 3.3, and an HDI monomer mass concentration of 0.2% by mass was obtained. For the obtained polyisocyanate composition (c-1), 13 The molar ratio of the urethane group / allophanate group determined by C-NMR measurement was 100 / 0.
[0388] [Synthesis example 2]
[0389] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was filled with a nitrogen atmosphere, and 100 parts of HDI and 33.2 parts of Capa2054 (manufactured by Ingevity; number average molecular weight 550, hydroxyl value 204, number of functional groups 2) as a polycaprolactone polyol were added. The temperature in the reactor was maintained at 100°C for 2 hours under stirring to carry out a urethane reaction. After the temperature was raised to 160°C, it was maintained for 1 hour to carry out an allophanate reaction. After filtering the cooled reaction solution, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (c-2) having an NCO content of 8.4% by mass, a viscosity of 1638 mPa.s at 25°C, a number average molecular weight of 1421, an average number of isocyanate groups of 2.8, and an HDI monomer mass concentration of 0.2% by mass was obtained. For the obtained polyisocyanate composition (c-2), 13 The molar ratio of the urethane group / allophanate group determined by C-NMR measurement was 93 / 7.
[0390] [Synthesis example 3]
[0391] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was filled with a nitrogen atmosphere, and 100 parts of HDI and 33.2 parts of Capa2054 (manufactured by Ingevity; number average molecular weight 550, hydroxyl value 204, number of functional groups 2) as a polycaprolactone polyol were added. The temperature in the reactor was maintained at 100°C for 2 hours under stirring to carry out a urethane reaction. After the temperature was raised to 160°C, it was maintained for 2 hours to carry out an allophanate reaction. After filtering the cooled reaction solution, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (c-3) having an NCO content of 9.5% by mass, a viscosity of 1628 mPa.s at 25°C, a number average molecular weight of 1528, an average number of isocyanate groups of 3.4, and an HDI monomer mass concentration of 0.2% by mass was obtained. For the obtained polyisocyanate composition (c-3), 13 The molar ratio of the urethane group / allophanate group determined by C-NMR measurement was 84 / 14.
[0392] [Synthesis Example 4]
[0393] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was placed in a nitrogen atmosphere, 100 parts of HDI and 33.7 parts of Capa2054 (manufactured by Ingevity; number average molecular weight 550, hydroxyl value 204, number of functional groups 2) as a polycaprolactone polyol were added, and the temperature in the reactor was maintained at 100°C for 2 hours under stirring to carry out a urethane reaction. After the temperature was raised to 160°C, it was maintained for 3 hours to carry out an allophanate reaction. After filtering the cooled reaction solution, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (c-4) having an NCO content of 9.8% by mass, a viscosity of 1695 mPa.s at 25°C, a number average molecular weight of 1559, an average number of isocyanate groups of 3.6, and an HDI monomer mass concentration of 0.2% by mass was obtained. For the obtained polyisocyanate composition (c-4), 13 The molar ratio of the urethane group / allophanate group determined by C-NMR measurement was 80 / 20.
[0394] [Synthesis Example 5]
[0395] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was placed in a nitrogen atmosphere, and 100 parts of HDI, 6.9 parts of polycaprolactone polyol (number average molecular weight 550, hydroxyl value 305, number of functional groups 3), and 12.8 parts of polytetramethylene glycol (number average molecular weight 1000, hydroxyl value 112, number of functional groups 2) were added. The temperature in the reactor was maintained at 90°C for 1 hour under stirring to carry out a urethane reaction. After filtering the cooled reaction liquid, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (c-5) having an NCO content of 8.9% by mass, a viscosity of 2740 mPa.s at 25°C, a number average molecular weight of 1570, an average number of isocyanate groups of 3.3, and an HDI monomer mass concentration of 0.2% by mass was obtained. For the obtained polyisocyanate composition (c-5), 13 The molar ratio of the urethane group / allophanate group determined by C-NMR measurement was 100 / 0.
[0396] [Synthesis example 6]
[0397] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was placed in a nitrogen atmosphere, 2700 parts of HDI and 210 parts of 2-ethylhexanol were added, and a urethanization reaction was carried out at 130° C. for 1 hour under stirring. Next, 0.54 parts of a 20% solid content mineral spirit solution of 2-ethylhexanoic acid zirconium oxysalt was added as an allophanation catalyst. When the refractive index of the reaction solution increased to 0.0055, 0.81 parts of a 50% isobutyl alcohol solution of dodecyl phosphate (a solution prepared by diluting isobutyl alcohol with trade name "JP-512" produced by Johoku Chemical Industry Co., Ltd.) (4.0 times the mole of the catalyst) was added to stop the reaction. After the cooled reaction solution was filtered, unreacted HDI was removed using a thin film evaporator. The obtained polyisocyanate was a transparent liquid, and a polyisocyanate composition (c-6) having an NCO content of 17.2% by mass, a viscosity of 110 mPa.s at 25° C., a number average molecular weight of 490, an average number of isocyanate groups of 2.0, and an HDI monomer mass concentration of 0.2% by mass was obtained. 13 The molar ratio of allophanate group / isocyanurate group determined by C-NMR measurement was 97 / 3.
[0398] [Comparative Synthesis Example 1]
[0399] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was placed in a nitrogen atmosphere, 100 parts of HDI and 33.2 parts of Capa2054 (manufactured by Ingevity; number average molecular weight 550, hydroxyl value 204, number of functional groups 2) as a polycaprolactone polyol were added, and the temperature in the reactor was maintained at 100° C. for 2 hours under stirring to carry out a urethanization reaction. After the temperature was raised to 130° C., 0.11 g of a 2-ethyl-1-hexanol solution containing 20% by mass of 2-ethylhexanoic acid zirconium oxysalt was added as an allophanation catalyst. When the refractive index of the reaction solution increased to 0.0028, 1.0 g of a 2-ethyl-1-hexanol solution containing 10% of pyrophosphoric acid in terms of solid content (a solution prepared by diluting "Phosphoric Acid (105%)" manufactured by Taihei Chemical Industry Co., Ltd. with 2-ethyl-1-hexanol) was added to stop the reaction. After the cooled reaction liquid was filtered, unreacted HDI was removed by a thin film evaporator. A polyisocyanate composition (c-7) having an NCO content of 9.0% by mass, a viscosity of 2980 mPa.s at 25°C, a number average molecular weight of 1520, an average number of isocyanate groups of 3.3, and an HDI monomer mass concentration of 0.2% by mass was obtained. 13 The molar ratio of the urethane group / allophanate group determined by C-NMR measurement was 70 / 30.
[0400] The crystallinity evaluation results of the obtained polyisocyanate compositions are shown in Table 3 below.
[0401] [Table 3]
[0402] Polyisocyanate composition c-1 c-2 c-6 Transmittance at 550nm (%) 42 94 81 evaluate B A A
[0403] <Manufacturing, coating and evaluation of coating composition (P)>
[0404] [Example 1]
[0405] The main agent (m c -1) 127.6 parts, polyisocyanate composition (c-1) 61.7 parts, and 6 parts of butyl acetate as a solvent were stirred and mixed with a disperser to obtain a coating composition (p-1).
[0406] [Examples 2 to 17, Comparative Examples 1 to 3]
[0407] Coating compositions (p-2) to (p-20) were obtained in the same manner as in Example 1 except that the main agent (MC) and the polyisocyanate composition (C) were changed as shown in Tables 3 and 4.
[0408] Various physical properties and evaluation results are shown in Tables 4 and 5 below.
[0409] [Table 4]
[0410]
[0411] [Table 5]
[0412]
[0413] The solid content concentration of the coating composition of Examples 1 to 17 and Comparative Examples 1 to 3 was 70% by weight or more.
[0414] Since the coating compositions of Examples 1 to 17 and Comparative Examples 1 to 3 have a high ratio of the main agent, the viscosity of the main agent was used to evaluate whether the viscosity increases at a high solid content concentration.
[0415] In Tables 4 and 5, the compounding amount of the matting agent (B) refers to the content ratio of the matting agent (B) relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2) and the polyisocyanate composition (C).
[0416] As described above, Examples 1 to 17 can suppress the viscosity of the main component (MC) to below 20,000 mPa·s even in a coating material having a high solid content concentration of 70 wt % or more, and can ensure the elongation of the obtained coating film at -20°C at a high level of 10% or more as the target.
[0417] In addition, regarding the matting property when formed into a coating film, the 60-degree gloss can be reduced with high matting efficiency, and the appearance of the obtained coating film is also good.
[0418] In addition, any of the coating compositions of Examples 1 to 7 in which the type of matting agent was changed to inorganic fine particles, organic polymer fine particles, organic polymer hollow particles, and wax particles achieved the target viscosity, matting efficiency when formed into a coating film, and coating film elongation at -20°C.
[0419] In Examples 10, 11, and 12 in which the amount of the matting agent was changed, as the amount was increased, the matting property of the coating film was improved, and the coating film elongation at -20°C at the target level was obtained.
[0420] On the other hand, in Comparative Examples 1 and 2 in which the polyisocyanate composition (C) as a curing agent used c-7 having a molar ratio of urethane group / alophanate group outside the range of the present invention, the matting efficiency was lower than that of Examples 8 and 12 containing the same amount of matting agent, and as a result, sufficient matting properties could not be obtained.
[0421] In Comparative Example 3 in which the amount of the matting agent was beyond the range of the present invention, the coating film elongation at -20°C was extremely reduced.
[0422] Hereinafter, the present embodiment will be described in more detail with reference to Examples, but the present embodiment is not limited to these Examples.
[0423] Details of materials used in Examples are as follows.
[0424] Organic polymer hollow particles (B-3): Matsumoto Microsphere FN-65DE, manufactured by Matsumoto Oil & Pharmaceutical Co., Ltd., average particle size = 55 μm, true specific gravity = 0.03
[0425] Organic polymer hollow particles (B-3): Matsumoto Microsphere MFL-81GTA, trade name, manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., average particle size = 20 μm, true specific gravity = 0.24
[0426] Organic polymer hollow particles (B-3): Matsumoto Microsphere MFL-81GCA, trade name, manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., average particle size = 18 μm, true specific gravity = 0.25
[0427] Organic polymer hollow particles (B-3): Matsumoto Microsphere MFL-30CA, trade name, manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., average particle size = 32 μm, true specific gravity = 0.15
[0428] Organic polymer hollow particles (B-3): Matsumoto Microsphere MFL-60CA, trade name, manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., average particle size = 61 μm, true specific gravity = 0.12
[0429] Organic polymer hollow particles (B-3): Matsumoto Microsphere MFL-110CAL, trade name, manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., average particle size = 99 μm, true specific gravity = 0.09
[0430] Organic polymer microparticles: TAFTIC AR650S manufactured by Japan Exlan Co., Ltd., average particle size = 18 μm, true specific gravity = 1.29
[0431] Aspartic acid ester compound (A-1): trade name "FEISPARTIC F-420" (manufactured by Shenzhen Feiyang Protech Co., Ltd.), solid content concentration 97%, amine value 201
[0432] Aspartic acid ester compound (A-1): trade name "FEISPARTIC F-520" (manufactured by Shenzhen Feiyang Protech Co., Ltd.), solid content concentration 97%, amine value 191
[0433] Hydroxyl-containing resin compound (A-2): trade name "ACRYDIC WGU-337" (manufactured by DIC Corporation), solid content concentration 69%, hydroxyl value 117
[0434] Pigment: Titanium oxide, trade name "TIPAQUE CR-97" (manufactured by Ishihara Sangyo Co., Ltd.)
[0435] Matting agent: precipitated silica, trade name "ACEMATT HK400" (manufactured by Evonik Japan Co., Ltd.), average particle size 6.3 μm
[0436] Matting agent: precipitated silica, trade name "Nipsil E-170" (manufactured by Tosoh Silica Co., Ltd.), average particle size 3.4 μm
[0437] Matting agent: precipitated silica, trade name "Nipsil E-1011" (manufactured by Tosoh Silica Co., Ltd.), average particle size 1.5 μm
[0438] Anti-settling agent: organic bentonite, trade name "Bentone SD-2" (manufactured by Elementis)
[0439] Dehydrating agent: Trade name Molecular Sieve 3A (manufactured by Union Showa Co., Ltd.)
[0440] Ultraviolet light absorber: Trade name: TINUVIN-1130 (manufactured by BASF)
[0441] Light stabilizer: Trade name TINUVIN-292 (manufactured by BASF)
[0442] Dispersant: Trade name BYK-163 (manufactured by BYK)
[0443] Defoamer: Trade name BYK-141 (manufactured by BYK)
[0444] Surface conditioner: BYK-331 (manufactured by BYK)
[0445] Solvent: Butyl acetate
[0446] <Measurement Methods of Physical Properties>
[0447] [Physical Properties 1A]
[0448] (Measurement of true specific gravity d1 of organic polymer hollow particles (B-3))
[0449] The true specific gravity d1 of the organic polymer hollow particles (B-3) is measured by the following method.
[0450] The true specific gravity was measured by a liquid immersion method (Archimedes method) using isopropyl alcohol in an atmosphere at an ambient temperature of 25° C. and a relative humidity of 50%.
[0451] Specifically, a volumetric flask with a capacity of 100cc is emptied, dried, and weighed (WB1(g)). The weighed volumetric flask is accurately filled with isopropyl alcohol until the curved liquid surface, and the weight of the volumetric flask filled with 100cc of isopropyl alcohol is weighed (WB2(g)). In addition, a volumetric flask with a capacity of 100cc is emptied, dried, and weighed (WS1(g)). The weighed volumetric flask is filled with about 50cc of organic polymer hollow particles (B) whose water content is adjusted to less than 1%, and the weight of the volumetric flask filled with the organic polymer hollow particles (B-3) is weighed (WS2(g)). Then, the weight of the volumetric flask filled with the organic polymer hollow particles (B-3) is weighed after accurately filling it with isopropyl alcohol until the curved liquid surface without the entry of bubbles (WS3(g)). Then, the true specific gravity (d1) of the organic polymer hollow particles (B-3) was calculated as the value of the true density (g / cc) obtained by substituting the obtained WB1, WB2, WS1, WS2 and WS3 into the following formula.
[0452] (True specific gravity d1 of organic polymer hollow particles (B-3)) = {(WS2-WS1) × (WB2-WB1) / 100} / {(WB2-WB1)-(WS3-WS2)}
[0453] [Physical properties 2A]
[0454] (Measurement of Average Particle Diameter of Organic Polymer Hollow Particles (B-3))
[0455] As a measuring device, the measurement was performed by a dry method using a laser diffraction particle size distribution measuring device (Mastersizer 3000) manufactured by Malvern. The average particle size was taken as the D50 value measured on a volume basis.
[0456] [Physical properties 3A]
[0457] (NCO content (mass %))
[0458] The NCO content (isocyanate content, mass %) of the polyisocyanate composition (C1) is determined as follows. Accurately weigh more than 1g and less than 3g (Wg) of the polyisocyanate composition manufactured by the manufacturing example in a conical flask, and then add 20mL of toluene to completely dissolve the polyisocyanate composition. Thereafter, add 10mL of a 2N toluene solution of di-n-butylamine, mix thoroughly, and leave at room temperature for 15 minutes. Furthermore, add 70mL of isopropanol to the solution and mix thoroughly. The solution is titrated with a 1N hydrochloric acid solution (factor F) using an indicator to obtain a titration value V2mL. For the same titration operation, a titration value V1mL is obtained without using a polyisocyanate. Based on the obtained titration value V2mL and titration value V1mL, the NCO content (mass %) of the polyisocyanate is calculated based on the following formula.
[0459] (NCO content (mass %)) = (V1-V2) × F × 42 / (W × 1000) × 100
[0460] [Physical properties 4A]
[0461] (Viscosity of polyisocyanate composition (C1) (mPa·s))
[0462] The viscosity of the polyisocyanate composition (C1) was measured at 25° C. using an E-type viscometer (trade name: RE-85R, manufactured by Toki Sangyo Co., Ltd.). A standard rotor (1°34′×R24) was used for the measurement. The rotation speed was set as follows.
[0463] (Speed)
[0464] 100r.pm (less than 128mPa·s)
[0465] 50r.pm (128mPa·s or more and less than 256mPa·s)
[0466] 20r.pm (256mPa·s or more and less than 640mPa·s)
[0467] 10r.pm (640mPa·s or more and less than 1280mPa·s)
[0468] 5r.pm (1280mPa·s or more and less than 2560mPa·s)
[0469] 2.5rpm (2560mPa·s or more and less than 5120mPa·s)
[0470] 1.0rpm (5184mPa·s or more and less than 12960mPa·s)
[0471] [Physical properties 5A]
[0472] (Number average molecular weight)
[0473] The number average molecular weight of the polyisocyanate composition (C1) is determined as a polystyrene-based number average molecular weight measured by gel permeation chromatography (hereinafter, abbreviated as “GPC”) using the following apparatus.
[0474] Device: "HLC-8120GPC" (trade name) manufactured by Tosoh Corporation
[0475] Column: "TSKgel SuperH1000" (trade name) manufactured by Tosoh Corporation × 1
[0476] "TSKgel SuperH2000" (trade name) × 1 piece
[0477] "TSKgel SuperH3000" (trade name) × 1 piece
[0478] Carrier: Tetrahydrofuran
[0479] Detection method: Differential refractometer
[0480] [Physical Properties 6A]
[0481] (Average number of isocyanate groups)
[0482] The average number of isocyanate groups in the polyisocyanate composition (C1) was calculated from [Physical Property 3] NCO content and [Physical Property 5A] number average molecular weight based on the following formula.
[0483] Average number of isocyanate groups = number average molecular weight × NCO content / 100 / 42
[0484] [Physical Properties 7A]
[0485] (Diisocyanate monomer mass concentration (mass %))
[0486] The mass concentration of diisocyanate in the polyisocyanate composition (C1) is determined as follows. Initially, place a 20 mL sample bottle on a digital balance and accurately weigh about 1 g of the sample. Then, add 0.03 to 0.04 g of nitrobenzene (internal standard solution) and weigh accurately. Finally, add about 9 mL of ethyl acetate, cover the lid and mix thoroughly to prepare the sample. Perform gas chromatography analysis on the prepared sample under the following conditions for quantification.
[0487] Device: GC-8A manufactured by Shimadzu
[0488] Column: "Silicone OV-17" manufactured by Shinwa Chemical Co., Ltd.
[0489] Column oven temperature: 120°C
[0490] Injection / detector temperature: 160°C
[0491] [Properties 8A]
[0492] (Viscosity of the main component (MC) for coating (mPa·s))
[0493] The viscosity of the obtained coating main agent (MC) was measured at 25° C. using an E-type viscometer (trade name: RE-85R or RE-85U, manufactured by Toki Sangyo Co., Ltd.). A standard rotor (RE-85R: 1°34'×R24, RE-85U: 3°×R14) was used for the measurement. The rotation speed was set as follows.
[0494] (Speed: RE-85R)
[0495] 100r.pm (less than 128mPa·s)
[0496] 50r.pm (128mPa·s or more and less than 256mPa·s)
[0497] 20r.pm (256mPa·s or more and less than 640mPa·s)
[0498] 10r.pm (640mPa·s or more and less than 1280mPa·s)
[0499] 5r.pm (1280mPa·s or more and less than 2560mPa·s)
[0500] 2.5rpm (2560mPa·s or more and less than 5120mPa·s)
[0501] (Speed: RE-85U)
[0502] 100r.pm (less than 5002mPa·s)
[0503] 50r.pm (5002mPa·s or more and less than 10.0Pa·s)
[0504] 20r.pm (10.0Pa·s or more and less than 25.01Pa·s)
[0505] 10r.pm (25.01Pa·s or more and less than 50.02Pa·s)
[0506] 5r.pm (50.02Pa·s or more and less than 100.0Pa·s)
[0507] 2.5rpm (100.0Pa·s or more and less than 200.1Pa·s)
[0508] (Evaluation Criteria)
[0509] S: 5000mPa·s or less
[0510] A: 5001mPa·s or more and less than 20000mPa·s (20.0Pa·s)
[0511] B: 20001mPa·s (20.0Pa·s) or more
[0512] [Properties 9]
[0513] (Solid content concentration (%) of coating composition (P))
[0514] After accurately weighing an aluminum pan with a bottom diameter of 38 mm, about 1 g of the coating composition (P) of the embodiment or comparative example was placed on the aluminum pan and accurately weighed (W1), and after adjusting to a uniform thickness, it was kept in an oven at 105° C. for 3 hours. After the aluminum pan reached room temperature, the coating composition remaining in the aluminum pan was accurately weighed (W2). Then, the obtained W1 and W2 were substituted into the following formula to calculate the solid content concentration (%) of the coating composition.
[0515] (Solid content concentration (%) of coating composition (P) = W2 / W1×100
[0516] <Evaluation method of coating film>
[0517] [Evaluation 1A]
[0518] (Appearance of coating film)
[0519] The coating composition (P) obtained in the examples and comparative examples was applied to a glass plate with an applicator to a dry film thickness of 40 μm or more and 60 μm or less. After coating, it was cured for 7 days under the conditions of 23° C. and 50% humidity to obtain each coating film. The appearance of each coating film was evaluated according to the following evaluation criteria.
[0520] (Evaluation Criteria)
[0521] S: The surface is very smooth and no bumps can be seen.
[0522] A: The surface is smooth, but a few small bumps can be seen.
[0523] B: There are many bumps and wrinkles on the surface.
[0524] [Rating 2A]
[0525] (Gloss of coating film)
[0526] The coating composition (P) obtained in the examples and comparative examples was applied to a glass plate with an applicator to a dry film thickness of 40 μm or more and 60 μm or less. After coating, it was cured for 7 days at 23° C. and 50% humidity to obtain each coating film. Then, the gloss value of the coating film was measured at 60 degrees -60 degrees using a gloss meter (Haze-Gloss, manufactured by BYK-Garner) and evaluated according to the following evaluation criteria.
[0527] (Evaluation Criteria)
[0528] A: Gloss value is below 40, good matte properties
[0529] B: Gloss value exceeds 40, and matte properties are insufficient
[0530] [Rating 3A]
[0531] (Alkali resistance of coating film)
[0532] The coating composition (P) obtained in the embodiment and the comparative example was applied to the glass plate with an applicator in such a manner that the dry film thickness was 40 μm or more and 60 μm or less. After coating, it was cured for 7 days at 23°C and 50% humidity to obtain each coating film. A rubber ring was placed on the obtained coating film, and a 10% by mass sodium hydroxide aqueous solution was dripped in the central part. After immersion at 23°C for 24 hours, the alkali resistance was evaluated according to the following evaluation criteria based on the state of bubbling generated between the glass substrate / coating film.
[0533] (Evaluation Criteria)
[0534] A: No change in appearance
[0535] B: White turbidity, dissolution, bubbling and swelling
[0536] <Manufacturing of main agent (MC) for coatings>
[0537] [Production Example 1A]
[0538] In a metal container, 33.5 parts of FEISPARTIC F-420 as an aspartic acid ester compound (A-1), 36.9 parts of TIPAQUE CR-97 as a pigment, 2.3 parts of BYK-163 as an additive, 0.35 parts of BYK-141, 1.8 parts of Bentone SD2, 3.5 parts of Molecular Sieve 3A (abbreviated as "MS 3A" in the table), and 21 parts of butyl acetate as a solvent were added, and then stirred and mixed with a disperser to obtain a mixture.
[0539] Next, the whole amount of the obtained mixture and glass beads (equivalent to the total mass of the mixture) were added to a disperser (manufactured by Taihei Systems Co., Ltd., tabletop SG MILL 1500W model), and the pigment was dispersed until the particle size of the pigment reached 20 μm or less to prepare a pigment dispersion paint. Furthermore, 19 parts of Matsumoto Microsphere MFL-81GTA as organic polymer hollow particles (B), 1.1 parts of TINUVIN-1130 as additives, 0.70 parts of TINUVIN-292, 0.12 parts of BYK-331, and 18 parts of butyl acetate as a solvent were added to 99.4 parts of the obtained pigment dispersion paint, and the mixture was stirred and mixed until uniform using a disperser to obtain a main agent for paint (mc-1).
[0540] [Manufacturing Examples 2A to 6A]
[0541] The same procedure as in [Production Example 1] was carried out except that the materials listed in Table 1 were used as the organic polymer hollow particles (B) to obtain coating base agents (mc-2) to (mc-6).
[0542] [Production Example 7A]
[0543] A coating base (mc-7) was obtained in the same manner as in [Production Example 2] except that the materials listed in Table 6 were used as the aspartic acid ester compound (A-1).
[0544] [Production Example 8A]
[0545] A coating base (mc-8) was obtained in the same manner as in [Production Example 2] except that the materials listed in Table 7 were used as the hydroxyl-containing resin compound (A-2) instead of the aspartic acid ester compound (A-1).
[0546] [Production Examples 9A to 14A]
[0547] Except having changed the compounding amount of a material as shown in Table 7, it carried out similarly to [Production Example 2A], and obtained the main agent (mc-9) - (mc-14) for coatings.
[0548] [Comparative Production Examples 1A to 5A]
[0549] Except having changed the kind and compounding amount of a material as shown in Table 8, it carried out similarly to [Production Example 1A], and obtained the main agent for coating (mc-15) - (mc-19).
[0550] [Table 6]
[0551]
[0552] [Table 7]
[0553]
[0554] [Table 8]
[0555]
[0556] <Production of Polyisocyanate Composition (C1)>
[0557] [Synthesis Example 1A]
[0558] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was filled with a nitrogen atmosphere, 100 parts of HDI and 33.7 parts of polycaprolactone triol having a number average molecular weight of 850 and a hydroxyl value of 198 were added, and the temperature in the reactor was maintained at 95° C. for 90 minutes under stirring to carry out a urethanization reaction. After the cooled reaction liquid was filtered, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (C1-1) having an NCO content of 9.0% by mass, a viscosity of 4980 mPa.s at 25° C., a number average molecular weight of 1520, an average number of isocyanate groups of 3.3, and an HDI monomer mass concentration of 0.2% by mass was obtained.
[0559] [Synthesis Example 2A]
[0560] A four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen blowing tube, and a dropping funnel was filled with a nitrogen atmosphere, and 100 parts of HDI, 6.9 parts of polycaprolactone triol with a number average molecular weight of 550 and a hydroxyl value of 305, and 12.8 parts of polytetramethylene glycol with a number average molecular weight of 1000 and a hydroxyl value of 112 were added. The temperature in the reactor was kept at 90° C. for 1 hour under stirring to carry out a urethanization reaction. After filtering the cooled reaction liquid, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (C1-2) having an NCO content of 8.9% by mass, a viscosity of 2740 mPa.s at 25° C., a number average molecular weight of 1570, an average number of isocyanate groups of 3.3, and an HDI monomer mass concentration of 0.2% by mass was obtained.
[0561] [Synthesis Example 3A]
[0562] A nitrogen atmosphere was set in a four-necked flask equipped with a stirrer, a thermometer, a reflux cooling tube, a nitrogen blowing tube, and a dropping funnel, 100 parts of HDI were added, and the temperature in the reactor was kept at 60°C under stirring. 0.15 parts of a solution prepared by diluting the isocyanurate reaction catalyst tetrabutylammonium acetate with 2-ethyl-1-hexanol to 10% by mass was added thereto, and the isocyanurate reaction was carried out. When the NCO content of the reaction solution reached 43.8% by mass, phosphoric acid was added to stop the reaction. Thereafter, the reaction solution was kept at 90°C for 1 hour. After filtering the cooled reaction solution, unreacted HDI was removed with a thin film evaporator. A polyisocyanate composition (C1-3) having an NCO content of 23.1% by mass, a viscosity of 1350 mPa.s at 25°C, a number average molecular weight of 590, an average number of isocyanate groups of 3.2, and an HDI monomer mass concentration of 0.1% by mass was obtained.
[0563] <Manufacturing, coating and evaluation of coating composition (P)>
[0564] [Example 1A]
[0565] 138.4 parts of the coating main agent (mc-1) obtained in Manufacturing Example 1A and Synthesis Example 1A, 61.7 parts of the polyisocyanate composition (C1-1), and 6 parts of butyl acetate as a solvent were placed in a metal container, and then stirred and mixed with a disperser to obtain a coating composition (p-1).
[0566] [Examples 2A to 16A] [Comparative Examples 1A to 5A]
[0567] Coating compositions (p-2) to (p-21) were obtained in the same manner as in Example 1A except that the coating base (MC) and the polyisocyanate composition (C) were changed as shown in Tables 9, 10 and 11.
[0568] Various physical properties and evaluation results are shown in Tables 9, 10, and 11 below.
[0569] [Table 9]
[0570]
[0571] [Table 10]
[0572]
[0573] [Table 11]
[0574]
[0575] As shown above, in the examples 1A to 16A that satisfy all the above-mentioned constitutions, the viscosity of the main agent (MC) is as low as 20,000 mPa·s or less, and the viscosity increase can be suppressed even in a coating having a high solid content concentration of 70% by weight or more. In addition, the matte property when formed into a coating film is also good, with a gloss of 40 or less at 60 degrees. Furthermore, the appearance and chemical resistance of the obtained coating film are also good.
[0576] In addition, in the comparison of the average particle size and specific gravity of the organic polymer hollow particles (Examples 1A to 6A), it was observed that the larger the average particle size, the more the matte properties when the coating film is made tend to be improved. On the other hand, it was observed that the higher the specific gravity, the more the viscosity of the main agent tends to be suppressed.
[0577] In addition, in the comparison of the examples (Example 9A, Example 12A, Example 13A, Example 14A) in which the blending amount of the organic polymer hollow particles was changed, it was observed that the greater the blending amount, the more the matte properties when the coating film was made tended to be improved. On the other hand, it was observed that the lower the blending amount, the more the viscosity of the main agent tended to be suppressed.
[0578] On the other hand, in the case of using silica, which is conventionally used as a matting agent (Comparative Example 1A and Comparative Example 2A), the following results were obtained: when the amount of silica added was increased, the viscosity became too high, and when the amount of silica added was reduced, sufficient matting properties could not be obtained. In addition, the chemical resistance was poor, and the appearance of the coating film was poor for the high-viscosity coating.
[0579] In addition, in the case where organic polymer fine particles having a large specific gravity were used instead of the organic polymer hollow particles (Comparative Example 5A), a result was obtained in which a sufficient matte property could not be obtained despite the low viscosity of the coating material.
[0580] In Comparative Examples 3A and 4A where the particle size of silica was changed, the viscosity was too high compared to Comparative Example 2A, and sufficient matte properties could not be obtained. In addition, the chemical resistance was poor, and the appearance of the coating film was poor.
[0581] Industrial Applicability
[0582] According to the coating composition of this embodiment, even in a coating having a high solid content concentration of 70% by weight or more, the viscosity increase can be suppressed by reducing the amount of matting agent added, and a coating film having an excellent matte appearance can be obtained efficiently. In addition, the elongation at a low temperature of about -20°C when the coating film is formed is good.
[0583] According to the coating composition of this embodiment, even in a coating having a high solid content concentration of 70% by weight or more, the viscosity increase is suppressed and an excellent matte appearance is obtained. In addition, the coating film has good chemical resistance.
Claims
1. A coating composition comprising a main agent, a matting agent (B), and a polyisocyanate composition (C), The main agent comprises either or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), The content ratio of the matting agent (B) is 1% by weight or more and 40% by weight or less relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2) and the polyisocyanate composition (C), The coating composition has a solid content concentration of 70% by weight or more. The polyisocyanate composition (C) comprises a polyisocyanate component (C-1), wherein the polyisocyanate component (C-1) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates and a polyester polyol having an average functional group number of 2 or 3 of hydroxyl groups, and the molar ratio of urethane group / alophanate group of the polyisocyanate component (C-1) is 100 / 0 to 75 / 25.
2. A coating composition comprising a main agent, a matting agent (B), and a polyisocyanate composition (C), The main agent comprises either or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), The content ratio of the matting agent (B) is 1% by weight or more and 40% by weight or less relative to the total amount of the aspartic acid ester compound (A-1), the hydroxyl-containing resin compound (A-2) and the polyisocyanate composition (C), The coating composition has a solid content concentration of 70% by weight or more. The polyisocyanate composition (C) comprises a polyisocyanate component (C-2), wherein the polyisocyanate component (C-2) is derived from one or more diisocyanates selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a polyester polyol having an average functional group number of 2 or 3 for hydroxyl groups, and a polyoxyalkylene polyol having an average functional group number of 2 to 4 for hydroxyl groups, and the molar ratio of urethane group / alophanate group of the polyisocyanate component (C-2) is 100 / 0 to 75 / 25.
3. The coating composition according to claim 1 or 2, wherein The matting agent (B) is at least one selected from the group consisting of inorganic fine particles (B-1), organic polymer fine particles (B-2), organic polymer hollow particles (B-3) and wax particles (B-4).
4. The coating composition according to claim 1 or 2, wherein The polyisocyanate composition (C) further comprises a polyisocyanate component (C-3), wherein the polyisocyanate component (C-3) is obtained from at least one diisocyanate selected from aliphatic diisocyanates and alicyclic diisocyanates and a monohydric alcohol having a carbon number of 1 to 20, and the molar ratio of the allophanate group to the isocyanurate group (allophonate group / isocyanurate group) of the polyisocyanate component (C-3) is 100 / 0 to 70 / 30.
5. The coating composition according to claim 1, wherein The molar ratio of the urethane group / allophanate group of the polyisocyanate component (C-1) is 99 / 1 to 90 / 10.
6. The coating composition according to claim 2, wherein The molar ratio of the urethane group / allophanate group of the polyisocyanate component (C-2) is 99 / 1 to 90 / 10.
7. A coating film formed by curing the coating composition according to claim 1 or 2.
8. A main agent for a coating, comprising one or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), and organic polymer hollow particles (B-3), The organic polymer hollow particles (B-3) have a true specific gravity of 0.01 or more and 0.30 or less, an average particle size of 1 μm or more and 100 μm or less, and a content of 10% by weight or more and 200% by weight or less relative to the total amount of one or both of the aspartic acid ester compound (A-1) and the hydroxyl-containing resin compound (A-2), The solid content concentration of the main agent for coating is 70% by weight or more.
9. The main agent for coating according to claim 8, wherein The organic polymer hollow particles (B-3) are either or both of hollow particles composed of an outer shell portion composed of a thermoplastic resin and a hollow portion surrounded by the outer shell portion, and particles whose surfaces are further coated with a thermosetting resin. 10 . A coating composition comprising the coating main agent according to claim 8 or 9 and a polyisocyanate composition (C1), wherein the coating composition has a solid content concentration of 70% by weight or more.
11. A coating film formed by curing the coating composition according to claim 10.
12. A coating curing agent, comprising a polyisocyanate composition (C1) and organic polymer hollow particles (B-3), The organic polymer hollow particles (B-3) have a true specific gravity of 0.01 to 0.30, an average particle size of 1 μm to 100 μm, and a content of 10% to 200% by weight relative to the total amount of the polyisocyanate composition (C1). The solid content concentration of the coating material curing agent is 70% by weight or more.
13. A method for imparting a matte appearance to a cured product of a coating composition, comprising adding organic polymer hollow particles (B-3) having a true specific gravity of 0.01 to 0.30 and an average particle size of 1 μm to 100 μm as a matting agent to the coating composition, wherein the coating composition comprises either or both of an aspartic acid ester compound (A-1) and a hydroxyl-containing resin compound (A-2), and a polyisocyanate composition (C1).
Citation Information
Patent Citations
Polyaspartic coating composition, coating film, and coated article
WO2018163953A1
Polyaspartic coating composition, coating film, and coated article
WO2018163959A1